Barrier film and polarizing plate with barrier film

By applying a barrier film composed of multiple layers of materials on the polarizing plate, the problem of discoloration of the polarizing plate under heating and humidification conditions is solved, and higher reliability is achieved.

CN119805646APending Publication Date: 2025-04-11NITTO DENKO CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411406682.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-10
Filing Date
2024-10-10
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing polarizing plate with anti-reflection layer is prone to discoloration under heating and humidification conditions, which affects its high reliability.

Method used

A barrier film is used, which consists of a transparent base film, a transparent resin film, a cured resin layer, a primer layer, a silicon oxide layer and an antifouling layer. The density of the silicon oxide layer is 2.35 g/cm3 or more to suppress discoloration of the polarizing plate.

Benefits of technology

Under heating and humidification conditions, the barrier film effectively suppresses the discoloration of the polarizing plate and improves its reliability in high temperature and high humidity environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119805646A_ABST
    Figure CN119805646A_ABST
Patent Text Reader

Abstract

The invention relates to a barrier film and a polarizing plate with the same. A barrier film (1) is provided with: a transparent base film (2); and a barrier layer (4) disposed on one side in the thickness direction of the transparent base film (2). The transparent substrate film (2) is provided with a transparent resin film (21). The barrier layer (4) is provided with at least one silicon oxide layer (42) and an antifouling layer (43) disposed on one side in the thickness direction of the silicon oxide layer (42). The density of the silicon oxide layer (42) closest to the antifouling layer (43) in the thickness direction is 2.35 g / cm3 or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a barrier film and a polarizing plate having the barrier film. Background Art

[0002] In image display devices such as liquid crystal displays and organic EL (Organic Electro-Luminescence) displays, a polarizing plate is disposed on at least one side of the display unit due to the image formation method. Such a polarizing plate is manufactured as described below. For example, a polarizing plate is formed on a resin substrate by coating a polyvinyl alcohol (PVA) resin on a resin substrate, and then stretched and dyed. Then, a protective film is attached to the obtained polarizing plate, and the resin substrate is removed. The polarizing plate manufactured by such a method has a thin polarizing plate, and by using the polarizing plate, the image display device can be made thinner.

[0003] Furthermore, for the purpose of protecting the polarizing plate, a polarizing plate with an antireflection layer obtained by laminating an antireflection film to such a polarizing plate has been proposed (for example, see Patent Document 1).

[0004] On the other hand, polarizing plates are required to have high reliability under heating and humidification conditions.

[0005] However, the polarizing plate with an antireflection layer described in Patent Document 1 has a disadvantage that the polarizing plate changes color under heating and humidification conditions.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: International Publication No. 2019 / 163461 Pamphlet Summary of the invention

[0009] An object of the present invention is to provide a barrier film capable of suppressing discoloration of a polarizing plate under heating and humidification conditions, and a polarizing plate with the barrier film.

[0010] The present invention [1] includes a barrier film, wherein the barrier film comprises: a transparent substrate film comprising a transparent resin film; and a barrier layer disposed on one side in a thickness direction of the transparent substrate film, the barrier layer comprising at least one silicon oxide layer and an antifouling layer disposed on one side in a thickness direction of the silicon oxide layer, wherein in the thickness direction, the density of the silicon oxide layer closest to the antifouling layer is 2.35 g / cm 3 above.

[0011] The present invention [2] includes the barrier film according to [1], wherein the transparent base film further comprises a cured resin layer disposed on one surface in the thickness direction of the transparent resin film.

[0012] The present invention [3] includes the barrier film as described in [1] or [2], wherein the barrier film further comprises a primer layer, the primer layer is a metal oxide layer, and the primer layer is arranged on one side in the thickness direction of the transparent base film and on the other side in the thickness direction of the barrier layer.

[0013] The present invention [4] includes the barrier film as described in any one of [1] to [3], wherein the barrier layer comprises: an alternating stack formed of at least one niobium oxide layer and at least one silicon oxide layer; and the antifouling layer is arranged on one surface of the alternating stack in the thickness direction.

[0014] The present invention [5] includes the barrier film according to any one of [1] to [3], wherein the barrier layer is formed of a silicon oxide layer and the antifouling layer disposed on one surface in the thickness direction of the silicon oxide layer.

[0015] The present invention [6] includes a polarizing plate with a barrier film, comprising: the barrier film according to any one of [1] to [5]; and a polarizing plate disposed on the other side in the thickness direction of the barrier film.

[0016] The present invention [7] includes the polarizing plate with a barrier film according to [6], wherein the polarizing plate comprises a protective film and a polarizer, and the polarizer is a coating film of a polyvinyl alcohol resin.

[0017] The present invention [8] comprises the polarizing plate with a barrier film as described in [6] or [7], wherein the change in chromaticity Δb of the transmitted light under the conditions of heating and humidification at 60°C and 90% RH for 240 hours is * Is below 0.5.

[0018] Effects of the Invention

[0019] The barrier film of the present invention comprises: a transparent substrate film comprising a transparent resin film and a cured resin layer disposed on one side of the transparent resin film in the thickness direction; and a barrier layer disposed on one side of the transparent substrate film in the thickness direction. The barrier layer comprises at least one silicon oxide layer and an antifouling layer disposed on one side of the silicon oxide layer in the thickness direction. In the thickness direction, the density of the silicon oxide layer closest to the antifouling layer is 2.35 g / cm 3 Therefore, when used for a polarizing plate, discoloration of the polarizing plate under heating and humidification conditions can be suppressed.

[0020] The polarizing plate with a barrier film of the present invention includes the barrier film described above, and thus, discoloration of the polarizing plate under heating and humidification conditions can be suppressed. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 A cross-sectional view showing one embodiment of the barrier film of the present invention.

[0022] Figure 2 express Figure 1 The method for producing the barrier film is shown in FIG. Figure 2 (A) represents a step of preparing a transparent resin film, Figure 2 (B) represents a step of forming a cured resin layer on a transparent resin film, Figure 2 (C) represents a step of forming a primer layer on the cured resin layer, Figure 2 (D) represents a step of forming an alternating stack of niobium oxide layers and silicon oxide layers on the primer layer, Figure 2 (E) shows a step of forming an antifouling layer on the silicon oxide layer.

[0023] Figure 3 Indicates that it is used Figure 1 sectional view of a polarizing plate with a barrier film showing a barrier film.

[0024] Figure 4 express Figure 3 A method for producing a polarizing plate with a barrier film is shown in . Figure 4 (A) represents a step of preparing a resin substrate, Figure 4 (B) represents a step of forming a coating film (polarizer) of a polyvinyl alcohol resin on a resin substrate, Figure 4 (C) represents a step of attaching a protective film to the polarizing plate via an adhesive layer, Figure 4 (D) represents a step of removing the resin substrate, Figure 4 (E) indicates that the protective film is attached to the surface Figure 1 The process of the barrier film is shown in FIG.

[0025] Figure 5 A schematic diagram showing the structure of a magnetron sputtering film-forming apparatus used in a method for producing a barrier film.

[0026] Figure 6 express Figure 5 FIG. 2 is an enlarged cross-sectional view of a magnetron plasma unit included in the magnetron sputtering film forming apparatus shown in FIG.

[0027] Figure 7 A cross-sectional view showing a magnet unit included in the first magnetron plasma unit.

[0028] Figure 8 A cross-sectional view showing a magnet unit included in the second magnetron plasma unit.

[0029] Fig. 9 A cross-sectional view showing a modified example of the polarizing plate with a barrier film.

[0030] Fig.10 express Fig. 9A method for producing a barrier film in a polarizing plate with a barrier film shown in . Fig.10 (A) represents a step of preparing a transparent resin film, Fig.10 (B) represents a step of forming a cured resin layer on a transparent resin film, Fig.10 (C) represents a step of forming a primer layer on the cured resin layer, Fig.10 (D) represents a step of forming a silicon oxide layer on the primer layer, Fig.10 (E) shows a step of forming an antifouling layer on the silicon oxide layer.

[0031] Description of Reference Numerals

[0032] 1: barrier film; 2: transparent substrate film; 3: primer layer; 4: barrier layer; 21: transparent resin film; 22: cured resin layer; 41: niobium oxide layer; 42: silicon oxide layer. DETAILED DESCRIPTION

[0033] 1. Barrier film

[0034] Reference Figure 1 , one embodiment of the barrier film of the present invention is described.

[0035] like Figure 1 As shown, the barrier film 1 is in a film shape (including a sheet shape) with a predetermined thickness. The barrier film 1 extends in a plane direction perpendicular to the thickness direction, and one surface (upper surface) and the other surface (lower surface) in the thickness direction of the barrier film 1 are flat.

[0036] The barrier film 1 includes: a transparent substrate film 2; and a barrier layer 4 disposed on one side in the thickness direction of the transparent substrate film 2. Furthermore, the barrier film 1 may include a primer layer 3 disposed on one side in the thickness direction of the transparent substrate film 2 and disposed on the other side in the thickness direction of the barrier layer 4. Specifically, Figure 1 As shown, the barrier film 1 includes: a transparent base film 2; a primer layer 3 disposed on one surface of the transparent base film 2 in the thickness direction; and a barrier layer 4 disposed on one surface of the primer layer 3 in the thickness direction.

[0037] <Transparent substrate film>

[0038] The transparent base film 2 is the lowermost layer of the barrier film 1. The transparent base film 2 includes a transparent resin film 21. In addition, the transparent base film 2 further includes a cured resin layer 22 disposed on one surface in the thickness direction of the transparent resin film 21 as required. The transparent base film 2 preferably includes a transparent resin film 21 and a cured resin layer 22 disposed on one surface in the thickness direction of the transparent resin film 21.

[0039] The transparent resin film 21 has a film shape (including a sheet shape). In addition, the transparent resin film 21 is, for example, a transparent resin film having flexibility.

[0040] As the material of the transparent resin film 21, for example, cellulose resin, polyester resin, (meth) acrylic resin (acrylic resin and / or methacrylic resin), olefin resin, polycarbonate resin, polyethersulfone resin, polyarylate resin, melamine resin, polyamide resin, polyimide resin, polystyrene resin, norbornene resin and polyvinyl alcohol resin can be listed. As polyester resin, for example, polyethylene terephthalate (PET), polybutylene terephthalate and polyethylene naphthalate can be listed. As polyolefin resin, for example, polyethylene, polypropylene and cycloolefin polymer (COP) can be listed. As cellulose resin, for example, cellulose triacetate (TAC) can be listed. From the viewpoints of transparency, heat resistance, mechanical strength, etc., the transparent resin film 21 preferably includes a cellulose film formed by a cellulose resin, and more preferably a cellulose triacetate film can be listed. It should be noted that the material of the transparent resin film 21 can be used alone or in combination of two or more.

[0041] The total light transmittance (JIS K-7105) of the transparent resin film 21 is, for example, 80% to 100%, preferably 85% to 100%, more preferably 88% to 100%, further preferably 90% to 100%.

[0042] The total light transmittance (JIS K-7105) of the transparent resin film 21 is, for example, 80% or more, preferably 85% or more, more preferably 88% or more, further preferably 90% or more, and for example, 100% or less.

[0043] The thickness of the transparent resin film 21 is not particularly limited, but is, from the viewpoint of strength and handleability, for example, 5 μm to 300 μm, preferably 10 μm to 250 μm, more preferably 20 μm to 200 μm, further preferably 30 μm to 170 μm, and particularly preferably 50 μm to 150 μm.

[0044] The thickness of the transparent resin film 21 is not particularly limited. From the viewpoint of strength and operability, it is, for example, 5 μm or more, preferably 10 μm or more, more preferably 20 μm or more, further preferably 30 μm or more, and particularly preferably 50 μm or more. In addition, it is, for example, 300 μm or less, preferably 250 μm or less, more preferably 200 μm or less, further preferably 170 μm or less, and particularly preferably 150 μm or less.

[0045] In addition, the thickness of the transparent resin film 21 can be measured using, for example, a film thickness meter.

[0046] The cured resin layer 22 is a layer that improves the mechanical properties of the barrier film 1. The cured resin layer 22 is in contact with the surface (one surface in the thickness direction) of the transparent resin film 21, for example.

[0047] Examples of the cured resin layer 22 include a hard coating layer and an anti-blocking layer. The hard coating layer, for example, prevents scratches on the exposed surface of the transparent resin film 21. The anti-blocking layer, for example, imparts blocking resistance to the surfaces of a plurality of barrier films 1 in contact with each other when the barrier films 1 are stacked in the thickness direction.

[0048] The cured resin layer 22 is, for example, a cured product of a curable resin composition. Specifically, the cured resin layer 22 can be formed by applying a curable resin composition to one surface in the thickness direction of the transparent resin film 21, drying it as needed, and then curing it.

[0049] The curable resin composition contains a curable resin. Examples of the curable resin include polyester resins, acrylic urethane resins, acrylic resins (excluding acrylic urethane resins), urethane resins (excluding acrylic urethane resins), amide resins, silicone resins, epoxy resins, and melamine resins. Preferably, acrylic resins (excluding acrylic urethane resins) and acrylic urethane resins are included. The curable resins may be used alone or in combination of two or more.

[0050] In addition, as a curable resin composition, for example, a UV-curable resin composition and a thermosetting resin composition can be listed. As a curable resin composition, from the viewpoint of manufacturing efficiency, a UV-curable resin composition is preferably used. The UV-curable resin composition contains at least one selected from the group consisting of a UV-curable monomer, a UV-curable oligomer, and a UV-curable polymer. As a specific example of a UV-curable resin composition, a hard coat forming composition described in Japanese Patent Publication No. 2016-179686 can be listed.

[0051] From the viewpoint of adjusting the hardness of the cured resin layer 22, adjusting the surface roughness, adjusting the refractive index, and imparting anti-glare properties, the curable resin composition preferably contains microparticles. As microparticles, for example, inorganic particles and organic particles can be listed, and preferably inorganic particles can be listed. As inorganic particles, for example, inorganic oxide particles can be listed. As materials for inorganic oxide particles, for example, silicon dioxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, tin oxide, indium oxide, cadmium oxide, and antimony oxide can be listed, and preferably silicon dioxide can be listed. As materials for organic particles, for example, polymethyl methacrylate, polystyrene, polyurethane, acrylic acid / styrene copolymer, benzoguanamine, melamine, and polycarbonate can be listed.

[0052] Furthermore, the curable resin composition preferably contains a photopolymerization initiator. Furthermore, the curable resin composition may contain additives such as a solvent, a leveling agent, a thixotropic agent, and an antistatic agent.

[0053] As a solvent, butyl acetate, ethyl acetate, toluene, and cyclopentanone are mentioned, for example, butyl acetate is preferably used.

[0054] The thickness of the cured resin layer 22 is, for example, 0.1 μm to 15 μm, preferably 0.5 μm to 12 μm, and more preferably 1 μm to 10 μm.

[0055] The thickness of the cured resin layer 22 is, for example, 0.1 μm or more, preferably 0.5 μm or more, more preferably 1 μm or more, and, for example, 15 μm or less, preferably 12 μm or less, more preferably 10 μm or less.

[0056] When the thickness of the cured resin layer 22 is equal to or greater than the lower limit, the cured resin layer 22 can be easily formed and the function of the cured resin layer 22 can be fully exerted. When the thickness of the cured resin layer 22 is equal to or less than the upper limit, the barrier film 1 can be made thinner.

[0057] From the viewpoint of improving the adhesion with the primer layer 3 described later or the barrier layer 4 described later, the surface in the thickness direction of the transparent substrate film 2 (the surface in the thickness direction of the cured resin layer 22) may be subjected to surface modification treatments such as corona treatment, plasma treatment, flame treatment, ozone treatment, primer treatment, glow treatment, saponification treatment, and treatment using a coupling agent.

[0058] The total light transmittance (JIS K-7105) of the transparent base film 2 is, for example, 80% to 100%, preferably 85% to 100%, more preferably 88% to 100%, further preferably 90% to 100%.

[0059] The total light transmittance (JIS K-7105) of the transparent base film 2 is, for example, 80% or more, preferably 85% or more, more preferably 88% or more, further preferably 90% or more, and for example, 100% or less.

[0060] The thickness of the transparent base film 2 is not particularly limited, but is, from the viewpoint of strength and handleability, for example, 5 to 300 μm, preferably 10 to 250 μm, more preferably 20 to 200 μm, further preferably 30 to 170 μm, and particularly preferably 50 to 150 μm.

[0061] The thickness of the transparent base film 2 is not particularly limited, and from the viewpoint of strength and operability, it is, for example, 5 μm or more, preferably 10 μm or more, more preferably 20 μm or more, further preferably 30 μm or more, and particularly preferably 50 μm or more, and is, for example, 300 μm or less, preferably 250 μm or less, more preferably 200 μm or less, further preferably 170 μm or less, and particularly preferably 150 μm or less.

[0062] <Primer layer>

[0063] The primer layer 3 is a bonding layer that improves the bonding property of the barrier layer 4 laminated on the transparent substrate film 2. The primer layer 3 is disposed on one side in the thickness direction of the transparent substrate film 2 and on the other side in the thickness direction of the barrier layer 4. That is, the primer layer 3 is disposed between the transparent substrate film 2 and the barrier layer 4. Specifically, Figure 1 As shown, the primer layer 3 is disposed on one surface in the thickness direction of the transparent base film 2 (one surface in the thickness direction of the cured resin layer 22). That is, the primer layer 3 is in contact with the transparent base film 2 (cured resin layer 22).

[0064] Examples of materials for the primer layer 3 include metals such as nickel, chromium, indium, aluminum, tin, gold, silver, platinum, zinc, titanium, tungsten, zirconium, and palladium, alloys of two or more of these metals, and oxides of these metals. In addition, examples of materials for the primer layer 3 include metalloids such as silicon and oxides thereof.

[0065] Examples of metal oxides include conductive oxides containing indium, conductive oxides containing antimony, and conductive oxides containing zinc. Examples of conductive oxides containing indium include indium tin composite oxide (ITO), indium zinc composite oxide (IZO), indium gallium composite oxide (IGO), and indium gallium zinc composite oxide (IGZO). Examples of conductive oxides containing antimony include antimony tin composite oxide (ATO). Examples of conductive oxides containing zinc include zinc aluminum composite oxide (AZO).

[0066] The material of the primer layer 3 is preferably an inorganic oxide containing at least one element selected from the group consisting of silicon, indium, aluminum, tin, titanium and zirconium. From the viewpoint of adhesion between the transparent substrate film 2 and the barrier layer 4 laminated on the primer layer 3, the material of the primer layer 3 is more preferably a metal oxide, and more preferably indium tin composite oxide (ITO). That is, the primer layer 3 is more preferably a metal oxide layer, and more preferably an ITO layer.

[0067] In ITO as a material for the primer layer, the content ratio of tin oxide to the total amount of indium oxide and tin oxide is, for example, 1 mass % to 50 mass %, preferably 3 mass % to 45 mass %, more preferably 5 mass % to 40 mass %, further preferably 10 mass % to 35 mass %.

[0068] In ITO as the material for the primer layer, the content ratio of tin oxide to the total amount of indium oxide and tin oxide is, for example, 1 mass % or more, preferably 3 mass % or more, more preferably 5 mass % or more, further preferably 10 mass % or more, and is, for example, 50 mass % or less, preferably 45 mass % or less, more preferably 40 mass % or less, further preferably 35 mass % or less.

[0069] The thickness of the primer layer 3 is, for example, 0.1 nm to 30.0 nm, preferably 0.5 nm to 20.0 nm, more preferably 1.0 nm to 15.0 nm, further preferably 2.0 nm to 10.0 nm, and particularly preferably 3.0 nm to 8.0 nm.

[0070] The thickness of the primer layer 3 is, for example, greater than 0.1 nm, preferably greater than 0.5 nm, more preferably greater than 1.0 nm, further preferably greater than 2.0 nm, and particularly preferably greater than 3.0 nm. It is also, for example, less than 30.0 nm, preferably less than 20.0 nm, more preferably less than 15.0 nm, further preferably less than 10.0 nm, and particularly preferably less than 8.0 nm.

[0071] When the thickness of the primer layer 3 is within the above range, adhesion between the transparent base film 2 and the barrier layer 4 laminated on the primer layer 3 can be ensured.

[0072] <Barrier layer>

[0073] The barrier layer 4 is a layer that improves the water vapor barrier property of the barrier film 1, thereby suppressing the discoloration of the polarizing plate under heating and humidification conditions. In addition, the barrier layer 4 is the uppermost layer of the barrier film 1. The barrier layer 4 is arranged on one side in the thickness direction of the transparent substrate film 2. Specifically, the barrier layer 4 is arranged on one side in the thickness direction of the primer layer 3. In other words, the barrier layer 4 is in contact with the primer layer 3.

[0074] The barrier layer 4 comprises at least one silicon oxide layer 42 and an antifouling layer 43 disposed on one side in the thickness direction of the silicon oxide layer 42. The barrier layer 4 preferably comprises: an alternating stacked body formed of at least one niobium oxide layer 41 and at least one silicon oxide layer 42; and an antifouling layer disposed on one side in the thickness direction of the alternating stacked body. Specifically, Figure 1As shown, the barrier layer 4 comprises, in order toward one side in the thickness direction: an alternating stack consisting of a niobium oxide layer 41a (first layer), a silicon oxide layer 42a (second layer), a niobium oxide layer 41b (third layer) and a silicon oxide layer 42b (fourth layer); and an antifouling layer 43.

[0075] The niobium oxide layer 41a (first layer) is in contact with the primer layer 3. The niobium oxide layer 41a (first layer) is in contact with the silicon oxide layer 42a (second layer). The silicon oxide layer 42a (second layer) is in contact with the niobium oxide layer 41b (third layer). The niobium oxide layer 41b (third layer) is in contact with the silicon oxide layer 42b (fourth layer).

[0076] It should be noted that the niobium oxide layer 41 is a layer formed of niobium oxide. In addition, the silicon oxide layer 42 is a layer formed of silicon oxide.

[0077] The niobium oxide layer 41 is a layer having a relatively large refractive index, and the silicon oxide layer 42 is a layer having a relatively small refractive index.

[0078] In such an alternately stacked structure, the intensity of reflected light is attenuated by interference between reflected light at multiple interfaces between the niobium oxide layer 41 and the silicon oxide layer 42. Such interference can be achieved by adjusting the optical film thickness (the product of the refractive index and the thickness) of the niobium oxide layer 41 and the silicon oxide layer 42.

[0079] The refractive index of the niobium oxide layer 41 at a wavelength of 550 nm is 2.33.

[0080] The thickness of the niobium oxide layer 41 a (first layer) is, for example, 1 nm to 50 nm, preferably 5 nm to 30 nm, and more preferably 8 nm to 20 nm.

[0081] The thickness of the niobium oxide layer 41 a (first layer) is, for example, greater than 1 nm, preferably greater than 5 nm, more preferably greater than 8 nm, and, for example, less than 50 nm, preferably less than 30 nm, more preferably less than 20 nm.

[0082] The thickness of the niobium oxide layer 41 b (third layer) is, for example, 5 nm to 200 nm, preferably 10 nm to 100 nm, more preferably 15 nm to 60 nm, and further preferably 20 nm to 40 nm.

[0083] The thickness of the niobium oxide layer 41b (third layer) is, for example, greater than 5 nm, preferably greater than 10 nm, more preferably greater than 15 nm, further preferably greater than 20 nm, and is, for example, less than 200 nm, preferably less than 100 nm, more preferably less than 60 nm, further preferably less than 40 nm.

[0084] The total thickness of the niobium oxide layer 41 is, for example, 1 nm to 300 nm, preferably 3 nm to 200 nm, and more preferably 5 nm to 100 nm.

[0085] The total thickness of the niobium oxide layer 41 is, for example, greater than or equal to 1 nm, preferably greater than or equal to 3 nm, more preferably greater than or equal to 5 nm, and is, for example, less than or equal to 300 nm, preferably less than or equal to 200 nm, more preferably less than or equal to 100 nm.

[0086] When the alternately stacked body includes the niobium oxide layer 41 a (first layer) and the niobium oxide layer 41 b (third layer), the thickness of the niobium oxide layer 41 a (first layer) is preferably thinner than the thickness of the niobium oxide layer 41 b (third layer).

[0087] When the alternating stack has a niobium oxide layer 41a (first layer) and a niobium oxide layer 41b (third layer), the ratio of the thickness of the niobium oxide layer 41a (first layer) to the total thickness of the niobium oxide layer 41 is, for example, 5% to 50%, preferably 15% to 45%, more preferably 20% to 42%, and further preferably 25% to 40%.

[0088] When the alternating stack has a niobium oxide layer 41a (first layer) and a niobium oxide layer 41b (third layer), the ratio of the thickness of the niobium oxide layer 41a (first layer) to the total thickness of the niobium oxide layer 41 is, for example, 5% or more, preferably 15% or more, more preferably 20% or more, further preferably 25% or more, and is, for example, less than 50%, preferably 45% or less, more preferably 42% or less, further preferably 40% or less.

[0089] When the alternating stack has a niobium oxide layer 41a (first layer) and a niobium oxide layer 41b (third layer), the ratio of the thickness of the niobium oxide layer 41b (third layer) to the total thickness of the niobium oxide layer 41 is, for example, 50% to 95%, preferably 55% to 85%, more preferably 58% to 80%, and further preferably 60% to 75%.

[0090] When the alternating stack has a niobium oxide layer 41a (first layer) and a niobium oxide layer 41b (third layer), the ratio of the thickness of the niobium oxide layer 41b (third layer) to the total thickness of the niobium oxide layer 41 is, for example, 50% or more, preferably 55% or more, more preferably 58% or more, further preferably 60% or more, and for example, 95% or less, preferably 85% or less, more preferably 80% or less, further preferably 75% or less.

[0091] The refractive index of the silicon oxide layer 42 at a wavelength of 550 nm is 1.46.

[0092] The thickness of the silicon oxide layer 42 a (second layer) is, for example, 1 nm to 300 nm, preferably 10 nm to 200 nm, and more preferably 20 nm to 150 nm.

[0093] The thickness of the silicon oxide layer 42 a (second layer) is, for example, greater than 1 nm, preferably greater than 10 nm, more preferably greater than 20 nm, and, for example, less than 300 nm, preferably less than 200 nm, more preferably less than 150 nm.

[0094] The thickness of the silicon oxide layer 42 b (fourth layer) is, for example, 10 nm to 300 nm, preferably 30 nm to 200 nm, more preferably 50 nm to 150 nm, and further preferably 70 nm to 120 nm.

[0095] The thickness of the silicon oxide layer 42b (fourth layer) is, for example, greater than 10 nm, preferably greater than 30 nm, more preferably greater than 50 nm, further preferably greater than 70 nm, and is, for example, less than 300 nm, preferably less than 200 nm, more preferably less than 150 nm, further preferably less than 120 nm.

[0096] The total thickness of the silicon oxide layer 42 is, for example, 20 nm to 500 nm, preferably 50 nm to 300 nm, more preferably 80 nm to 200 nm, and further preferably 100 nm to 150 nm.

[0097] The total thickness of the silicon oxide layer 42 is, for example, greater than 20 nm, preferably greater than 50 nm, more preferably greater than 80 nm, further preferably greater than 100 nm, and is, for example, less than 500 nm, preferably less than 300 nm, more preferably less than 200 nm, further preferably less than 150 nm.

[0098] When the alternately stacked body includes the silicon oxide layer 42a (second layer) and the silicon oxide layer 42b (fourth layer), the thickness of the silicon oxide layer 42a (second layer) is preferably thinner than the thickness of the silicon oxide layer 42b (fourth layer).

[0099] In the case where the alternating stack has a silicon oxide layer 42a (second layer) and a silicon oxide layer 42b (fourth layer), the ratio of the thickness of the silicon oxide layer 42a (second layer) to the total thickness of the silicon oxide layer 42 is, for example, 1% to 50%, preferably 10% to 45%, more preferably 15% to 40%, and further preferably 20% to 35%.

[0100] In the case where the alternating stack has a silicon oxide layer 42a (second layer) and a silicon oxide layer 42b (fourth layer), the ratio of the thickness of the silicon oxide layer 42a (second layer) to the total thickness of the silicon oxide layer 42 is, for example, greater than 1%, preferably greater than 10%, more preferably greater than 15%, further preferably greater than 20%, and is, for example, less than 50%, preferably less than 45%, more preferably less than 40%, further preferably less than 35%.

[0101] In the case where the alternating stack has a silicon oxide layer 42a (second layer) and a silicon oxide layer 42b (fourth layer), the ratio of the thickness of the silicon oxide layer 42b (fourth layer) to the total thickness of the silicon oxide layer 42 is, for example, 50% to 99%, preferably 55% to 90%, more preferably 60% to 85%, and further preferably 65% ​​to 80%.

[0102] In the case where the alternating stack has a silicon oxide layer 42a (second layer) and a silicon oxide layer 42b (fourth layer), the ratio of the thickness of the silicon oxide layer 42b (fourth layer) to the total thickness of the silicon oxide layer 42 is, for example, greater than 50%, preferably greater than 55%, more preferably greater than 60%, further preferably greater than 65%, and for example, less than 99%, preferably less than 90%, more preferably less than 85%, further preferably less than 80%.

[0103] The total thickness of the alternately stacked body is, for example, 50 nm to 800 nm, preferably 80 nm to 500 nm, more preferably 100 nm to 400 nm, further preferably 120 nm to 300 nm, and particularly preferably 130 nm to 250 nm.

[0104] The total thickness of the alternating stack is, for example, greater than 50 nm, preferably greater than 80 nm, more preferably greater than 100 nm, further preferably greater than 120 nm, and particularly preferably greater than 130 nm. It is also, for example, less than 800 nm, preferably less than 500 nm, more preferably less than 400 nm, further preferably less than 300 nm, and particularly preferably less than 250 nm.

[0105] When the total thickness of the alternating laminate is equal to or greater than the lower limit, the intensity of reflected light can be attenuated. When the total thickness of the alternating laminate is equal to or less than the upper limit, cracking of the alternating laminate can be suppressed.

[0106] The ratio of the thickness (total thickness) of the niobium oxide layer 41 to the total thickness of the alternating stack is, for example, 1% to 80%, preferably 3% to 60%, more preferably 10% to 40%, further preferably 15% to 35%, and particularly preferably 20% to 30%.

[0107] The ratio of the thickness (total thickness) of the niobium oxide layer 41 to the total thickness of the alternating stack is, for example, greater than 1%, preferably greater than 3%, more preferably greater than 10%, further preferably greater than 15%, particularly preferably greater than 20%, and is, for example, less than 80%, preferably less than 60%, more preferably less than 40%, further preferably less than 35%, and particularly preferably less than 30%.

[0108] The ratio of the thickness (total thickness) of the silicon oxide layer 42 to the total thickness of the alternating stack is, for example, 20% to 99%, preferably 40% to 97%, more preferably 60% to 90%, further preferably 65% ​​to 85%, and particularly preferably 70% to 80%.

[0109] The ratio of the thickness (total thickness) of the silicon oxide layer 42 to the total thickness of the alternating stack is, for example, greater than 20%, preferably greater than 40%, more preferably greater than 60%, further preferably greater than 65%, particularly preferably greater than 70%, and is, for example, less than 99%, preferably less than 97%, more preferably less than 90%, further preferably less than 85%, and particularly preferably less than 80%.

[0110] One surface in the thickness direction of the alternately laminated body (the surface in contact with the antifouling layer 43) may be subjected to a surface modification treatment. Examples of the surface modification treatment include corona treatment, plasma treatment, ozone treatment, primer treatment, glow treatment, and coupling agent treatment.

[0111] The surface roughness Ra (arithmetic mean surface roughness) of one surface in the thickness direction of the alternately laminated body (the surface in contact with the antifouling layer 43 ) is, for example, 0.5 nm to 10 nm, or preferably 0.8 nm to 8 nm.

[0112] The surface roughness Ra (arithmetic mean surface roughness) of one surface in the thickness direction of the alternately stacked body (the surface in contact with the antifouling layer 43 ) is, for example, 0.5 nm or more, preferably 0.8 nm or more, and for example, 10 nm or less, preferably 8 nm or less.

[0113] In addition, the surface roughness Ra can be obtained from an observation image of a 1 μm square using an AFM (atomic force microscope).

[0114] In the thickness direction, the density of the silicon oxide layer 42 closest to the antifouling layer 43 is, for example, 2.35 g / cm 3 ~2.50g / cm 3 , preferably 2.35 g / cm 3 ~2.47g / cm 3 , more preferably 2.37 g / cm 3 ~2.45g / cm 3, more preferably 2.39 g / cm 3 ~2.45g / cm 3 In addition, it is preferable that the density is the same in the other silicon oxide layers 42 as well.

[0115] The density of the silicon oxide layer 42 closest to the antifouling layer 43 in the thickness direction is 2.35 g / cm 3 Above, preferably 2.37 g / cm 3 More preferably, 2.39 g / cm 3 Above, for example, 2.50 g / cm 3 Below, preferably 2.47 g / cm 3 Below, more preferably 2.45g / cm 3 the following.

[0116] In the thickness direction, if the density of the silicon oxide layer 42 closest to the antifouling layer 43 is greater than the above lower limit, the water vapor barrier property of the barrier film 1 can be improved, and the discoloration of the polarizing plate under heating and humidification conditions can be suppressed. It should be noted that the density of each layer can be obtained by the method described in the examples described below.

[0117] The density of the niobium oxide layer 41 is, for example, 4.00 g / cm 3 ~5.00g / cm 3 .

[0118] The density of the niobium oxide layer 41 is, for example, 4.00 g / cm 3 Above, for example, 5.00 g / cm 3 the following.

[0119] The antifouling layer 43 is a layer that prevents contamination from the external environment and facilitates removal of attached contaminants. The antifouling layer 43 is also a layer having water vapor barrier properties. The antifouling layer 43 is the uppermost layer of the barrier film 1.

[0120] As the material of the antifouling layer 43, an organic fluorine compound having a terminal structure (terminal structure E) represented by the chemical formula CF3OCF2- is used. That is, the antifouling layer 43 contains an organic fluorine compound having a terminal structure E. As such an organic fluorine compound, an alkoxysilane compound having a perfluoropolyether skeleton is preferably used. As an alkoxysilane compound having a terminal structure E and a perfluoropolyether skeleton, for example, a compound represented by the following general formula (1) can be cited.

[0121] CF3-OCF2-R1-X-(CH2) m -Si(OR2)3(1)

[0122] R1 represents a structure containing at least one repeating structure of a perfluoropolyether (PFPE) group, preferably a structure containing two repeating structures of PFPE groups. Examples of the repeating structure of the PFPE group include a repeating structure of a linear PFPE group and a repeating structure of a branched PFPE group. Examples of the repeating structure of the linear PFPE group include -(OC n F 2n ) p -(n represents an integer of 1 to 20, and p represents an integer of 1 to 100. The same shall apply hereinafter). Examples of the repeating structure of the branched PFPE group include -(OC(CF3)2) p - The structure represented and - (OCF2CF(CF3)CF2) p As the repeating structure of the PFPE group, preferably, a repeating structure of a linear PFPE group can be cited, and more preferably, -(OCF2) p - and - (OC2F4) p -. R2 is, for example, an alkyl group having 1 to 4 carbon atoms, preferably a methyl group. X is, for example, an ether group, a carbonyl group, an amino group, and an amide group, preferably an ether group. m is, for example, an integer of 1 to 20, preferably an integer of 1 to 10, and more preferably an integer of 1 to 5.

[0123] The alkoxysilane compound having a perfluoropolyether skeleton may be used alone or in combination of two or more.

[0124] When the material of the antifouling layer 43 contains an alkoxysilane compound having a perfluoropolyether skeleton, the antifouling function of the antifouling layer 43 can be enhanced.

[0125] The water contact angle (pure water contact angle) of the outer surface (exposed surface) of the antifouling layer 43 is, for example, 110° to 130°, preferably 111° to 130°, more preferably 112° to 130°, further preferably 113° to 130°, and particularly preferably 114° to 130°.

[0126] The water contact angle (pure water contact angle) of the outer surface (exposed surface) of the antifouling layer 43 is, for example, 110° or more, preferably 111° or more, more preferably 112° or more, further preferably 113° or more, particularly preferably 114° or more, and for example, 130° or less.

[0127] When the water contact angle of the outer surface of the antifouling layer 43 is equal to or greater than the above lower limit, the antifouling layer 43 has high antifouling properties.

[0128] It should be noted that the water contact angle can be obtained by forming water droplets (pure water droplets) with a diameter of less than 2 mm on the outer surface of the antifouling layer 43 and measuring the contact angle of the water droplets with respect to the outer surface of the antifouling layer 43. The water contact angle of the outer surface of the antifouling layer 43 can be adjusted, for example, by the composition of the antifouling layer 43, the roughness of the outer surface, and the composition of other layers.

[0129] The thickness of the antifouling layer 43 is, for example, 1 nm to 100 nm, preferably 3 nm to 50 nm, more preferably 5 nm to 20 nm, and further preferably 6 nm to 12 nm.

[0130] The thickness of the antifouling layer 43 is, for example, 1 nm or more, preferably 3 nm or more, more preferably 5 nm or more, further preferably 6 nm or more, and is, for example, 100 nm or less, preferably 50 nm or less, more preferably 20 nm or less, further preferably 12 nm or less.

[0131] It is preferable that the antifouling layer 43 has a small difference in refractive index with the layer in contact with the antifouling layer 43. Specifically, when the antifouling layer 43 is in contact with the silicon oxide layer 42, the refractive index of the antifouling layer 43 is, for example, 1.6 or less, and preferably 1.55 or less.

[0132] The thickness of the barrier film 1 is, for example, 5 μm to 300 μm, preferably 10 μm to 250 μm, more preferably 20 μm to 200 μm, further preferably 30 μm to 170 μm, and particularly preferably 50 μm to 150 μm.

[0133] The thickness of the barrier film 1 is, for example, 5 μm or more, preferably 10 μm or more, more preferably 20 μm or more, further preferably 30 μm or more, particularly preferably 50 μm or more, and is, for example, 300 μm or less, preferably 250 μm or less, more preferably 200 μm or less, further preferably 170 μm or less, particularly preferably 150 μm or less.

[0134] The reflectance of the barrier film 1 is, for example, 0.0% to 8.0%, preferably 0.0% to 5.0%, more preferably 0.0% to 4.0%, further preferably 0.0% to 2.0%, and particularly preferably 0.0% to 1.0%.

[0135] The reflectance of the barrier film 1 is, for example, 0.0% or more, and for example, 8.0% or less, preferably 5.0% or less, more preferably 4.0% or less, further preferably 2.0% or less, and particularly preferably 1.0% or less.

[0136] It should be noted that the reflectance of the barrier film 1 can be measured using an ultraviolet-visible-infrared spectrophotometer.

[0137] 2. Barrier film manufacturing method

[0138] Reference Figure 2 (A)~ Figure 2 (E) The method for producing the barrier film of the present invention is described.

[0139] The method for manufacturing the barrier film 1 includes, for example, a preparation step ( Figure 2 (A)), preparing a transparent resin film 21; curing resin layer forming step ( Figure 2 (B)), forming a cured resin layer 22 on the transparent resin film 21; primer layer forming step ( Figure 2 (C)), forming a primer layer 3 on the cured resin layer 22; alternating laminate formation step ( Figure 2 (D)), forming an alternating stack of niobium oxide layers 41 and silicon oxide layers 42 on the primer layer 3; and an antifouling layer forming step ( Figure 2 (E)), an antifouling layer 43 is formed on the alternating laminate. It should be noted that the primer layer forming step and the alternating laminate forming step are performed using the following steps: Figure 5 The device Z shown is implemented sequentially.

[0140] <Preparation process>

[0141] In the preparation process, Figure 2 As shown in (A), a transparent resin film 21 is prepared.

[0142] <Step of forming a cured resin layer>

[0143] In the curing resin layer forming step, Figure 2 As shown in (B), a cured resin layer 22 is formed on one surface in the thickness direction of the transparent resin film 21. Specifically, the above-mentioned curable resin composition is applied to one surface in the thickness direction of the transparent resin film 21 to form a coating film, and then the coating film is cured to form the cured resin layer 22.

[0144] When the curable resin composition contains a solvent, the coating film on the transparent resin film 21 is dried after the curable resin composition is applied.

[0145] The drying temperature is, for example, 50° C. to 120° C. Moreover, the drying time is, for example, 10 seconds to 10 minutes.

[0146] When the curable resin composition contains an ultraviolet curable resin, the coating on the transparent resin film 21 is cured by ultraviolet irradiation. Examples of the light source for ultraviolet irradiation include a high pressure mercury lamp and an LED lamp. The cumulative irradiation amount of ultraviolet light is, for example, 100 mJ / cm 2 ~500mJ / cm 2 .

[0147] As described above, a transparent base film 2 is obtained which has a cured resin layer 22 on one side in the thickness direction of the transparent resin film 21. In the present embodiment, a roll of the transparent base film 2 is prepared. Specifically, the transparent base film 2 is rolled up in such a manner that the surface of the transparent base film 2 on the cured resin layer 22 side faces the inner side of the roll radial direction.

[0148] [Device Z]

[0149] In the method for producing the barrier film 1, the primer layer forming step and the alternately laminated body forming step are sequentially performed while the transparent base film 2 is transported as a working film W in a roll-to-roll manner under a reduced pressure environment. Figure 5 , a magnetron sputtering film forming apparatus Z is described as an example of an apparatus for performing the primer layer forming step and the alternately stacked body forming step.

[0150] like Figure 5 As shown, the device Z includes a transport unit P1 and a film forming unit P2.

[0151] The transport section P1 includes a transport housing 51 , a feed roller 52 , a take-up roller 53 , a guide roller 54 , and a vacuum pump 55 .

[0152] The conveyance housing 51 has a substantially box shape extending in the conveyance direction and accommodates a feed roller 52 , a take-up roller 53 , and a guide roller 54 .

[0153] The delivery roller 52 is arranged at the upstream end in the conveying direction in the conveying housing 51, and the winding roller 53 is arranged at the downstream end in the conveying direction in the conveying housing 51. The roll of the transparent base film 2 is mounted on the delivery roller 52 as the working film W. The winding roller 53 is a roller for winding the working film W. A plurality of guide rollers 54 are arranged between the delivery roller 52 and the winding roller 53. The plurality of guide rollers 54 are arranged so that the transparent base film 2 is wound around the film forming roller 63.

[0154] The vacuum pump 55 is provided in the transport housing 51 .

[0155] The film forming section P2 includes a film forming housing 61 , a film forming roller 63 , and a plurality of magnetron plasma units 64 .

[0156] The film forming housing 61 is continuous with the conveying housing 51, and together with the conveying housing 51, forms a vacuum chamber. The film forming housing 61 has a substantially box-like shape. The film forming housing 61 has a plurality of partition walls 62. The plurality of partition walls 62 extend toward the film forming roller 63. It should be noted that a sputtering gas supply device (not shown) is provided in the film forming housing 61. The film forming housing 61 accommodates the film forming roller 63 and a plurality of magnetron plasma units 64.

[0157] The axis of the film-forming roller 63 extends along the width direction that is orthogonal to the conveyance direction and the thickness direction of the transparent base film 2 .

[0158] The plurality of magnetron plasma units 64 are disposed so as to face each other on the radially outer side of the film-forming roller 63. The plurality of magnetron plasma units 64 are disposed so as to be spaced apart from each other along the circumferential direction of the film-forming roller 63.

[0159] The magnetron plasma units 64 adjacent to each other in the circumferential direction are separated by the partition wall 62. The space separated by the partition wall 62 constitutes the film forming chamber R. The film forming chamber R is divided into a plurality of chambers (for example, a first film forming chamber R1, a second film forming chamber R2, a third film forming chamber R3, and a fourth film forming chamber R4) in the film forming housing 61 (vacuum chamber). A magnetron plasma unit 64 is provided in one film forming chamber R. Figure 6 As shown, each of the plurality of magnetron plasma units 64 includes a plasma housing 71 , a first unit 72 , and a second unit 73 .

[0160] The plasma housing 71 has a substantially box-like shape with one side open toward the film-forming roller 63. The plasma housing 71 extends along the axis of the film-forming roller 63. The plasma housing 71 accommodates the first unit 72 and the second unit 73. The first unit 72 and the second unit 73 are adjacently arranged with a gap therebetween along the circumferential direction of the film-forming roller 63. The first unit 72 and the second unit 73 face the film-forming roller 63 via the opening of the plasma housing 71.

[0161] The first unit 72 and the second unit 73 have the same structure except for the rotation direction of the rotating target 74 (described later). Figure 6 to Figure 8 , the first unit 72 is described in detail, and the second unit 73 is described briefly. It should be noted that, Figure 7 75 of the first magnetron plasma unit 64 for forming the primer layer 3, Figure 8 The magnet unit 75 included in the second magnetron plasma unit 64 for forming the niobium oxide layer 41 and the silicon oxide layer 42 is shown.

[0162] like Figure 6 As shown, the first unit 72 includes a rotating target 74 and a magnet unit 75 .

[0163] The rotating target 74 has a cylindrical shape and has an axis AL (center when viewed in cross section, see FIG. 5 ) parallel to the axis of the film-forming roller 63. Figure 7 and Figure 8). The rotating target 74 can rotate in a direction opposite to the rotation direction of the film-forming roller 63 (can move in a circle). The rotating target 74 is electrically connected to a cathode source (not shown) and can thus function as a cathode. In addition, a target material is stacked on the outer peripheral surface of the rotating target 74. Examples of the target material include: the material of the primer layer 3 described above, niobium (the material of the niobium oxide layer 41), and silicon (the material of the silicon oxide layer 42).

[0164] The magnet unit 75 is accommodated on the radially inner side of the rotating target 74. Figure 7 and Figure 8 As shown, the magnet unit 75 includes a fixing member 80 , two first magnets 81 , and two second magnets 82 .

[0165] The fixing member 80 has a narrow plate shape extending in the axial direction of the film-forming roller 63, and is called a yoke. The surface of the fixing member 80 on one side in the thickness direction (the main surface 83 on one side) and the surface on the other side in the thickness direction (the main surface on the other side) are both flat surfaces. The main surface 83 on one side is opposite to the film-forming roller 63. The main surface on the other side is parallel to the main surface on one side. Examples of the material of the fixing member 80 include metals such as iron.

[0166] The two first magnets 81 and the two second magnets 82 each have a quadrangular prism shape extending along the axial direction of the film forming roller 63. The two first magnets 81 and the two second magnets 82 are each fixed to a main surface 83 of one side of the fixing member 80. The two first magnets 81 and the two second magnets 82 are each arranged adjacent to each other in the width direction of the fixing member 80. Specifically, the two first magnets 81 and the two second magnets 82 are each in contact with each other in the width direction.

[0167] The two first magnets 81 and the two second magnets 82 include a first magnetic pole portion 91 , a second magnetic pole portion 92 , a third magnetic pole portion 93 and a fourth magnetic pole portion 94 in a cross-sectional view along the width direction and the thickness direction of the fixed member 80 (corresponding to the direction orthogonal to the axis of the rotating target 74 ).

[0168] The first magnetic pole portion 91, the second magnetic pole portion 92, the third magnetic pole portion 93, and the fourth magnetic pole portion 94 are sequentially arranged along one circumferential direction (the rotation direction of the rotating target 74). The first magnetic pole portion 91, the second magnetic pole portion 92, the third magnetic pole portion 93, and the fourth magnetic pole portion 94 are sequentially arranged toward one side in the width direction of the fixing member 80 so as to contact each other.

[0169] The second magnetic pole portion 92 and the third magnetic pole portion 93 are constituted by two first magnets 81. For their part, the second magnetic pole portion 92 and the third magnetic pole portion 93 have, for example, N poles. The first magnetic pole portion 91 and the fourth magnetic pole portion 94 are constituted by, for example, the second magnet 82. The first magnetic pole portion 91 and the fourth magnetic pole portion 94 have, for example, S poles.

[0170] In cross-sectional view, the first magnetic pole portion 91, the second magnetic pole portion 92, the third magnetic pole portion 93, and the fourth magnetic pole portion 94 each have a substantially rectangular shape of the same shape. In cross-sectional view, the first magnetic pole portion 91, the second magnetic pole portion 92, the third magnetic pole portion 93, and the fourth magnetic pole portion 94 each have a substantially rectangular shape, and the substantially rectangular shape has: a fixed side fixed to a main surface 83 of one side of the fixed member 80; an opposite side located on the side opposite to the fixed side; and two side sides connecting the two end edges of the fixed side and the opposite side.

[0171] The fixed sides of the first magnetic pole portion 91, the second magnetic pole portion 92, the third magnetic pole portion 93, and the fourth magnetic pole portion 94 are arranged on one main surface 83 of the fixing member 80. The opposite sides of the first magnetic pole portion 91, the second magnetic pole portion 92, the third magnetic pole portion 93, and the fourth magnetic pole portion 94 are parallel to the one main surface 83 of the fixing member 80. The opposite sides of the first magnetic pole portion 91, the second magnetic pole portion 92, the third magnetic pole portion 93, and the fourth magnetic pole portion 94 are continuous in the width direction, specifically, in the same plane (forming one flat surface).

[0172] The thickness direction length and width direction length of each of the first magnetic pole portion 91 , the second magnetic pole portion 92 , the third magnetic pole portion 93 , and the fourth magnetic pole portion 94 differ according to the set sputtering angle.

[0173] exist Figure 7 In the magnet unit 75 of the first magnetron plasma unit 64 shown in the figure, the thickness direction length and width direction length of each of the first magnetic pole portion 91, the second magnetic pole portion 92, the third magnetic pole portion 93 and the fourth magnetic pole portion 94, that is, the ratio (D / L) of the separation distance D (the length of the side) between the opposite side and the fixed side to the length L of the opposite side is, for example, 0.8 to 1.2, preferably 0.9 to 1.1, and more preferably 1.0.

[0174] exist Figure 7 In the magnet unit 75 of the first magnetron plasma unit 64 shown in the figure, the thickness direction length and width direction length of each of the first magnetic pole portion 91, the second magnetic pole portion 92, the third magnetic pole portion 93 and the fourth magnetic pole portion 94, that is, the ratio (D / L) of the separation distance D (the length of the side) between the opposite side and the fixed side to the length L of the opposite side is, for example, greater than 0.8, preferably greater than 0.9, and for example, less than 1.2, preferably less than 1.1.

[0175] exist Figure 7 In the magnet unit 75 included in the first magnetron plasma unit 64 shown in FIG. 8 , the first magnetic pole portion 91 , the second magnetic pole portion 92 , the third magnetic pole portion 93 , and the fourth magnetic pole portion 94 preferably have the same length in the thickness direction and the same length in the width direction.

[0176] When the ratio (D / L) is in the above range, the sputtering angle (angle θ) shown below is obtained.

[0177] exist Figure 7 In the magnet unit 75 included in the first magnetron plasma unit 64 shown in FIG, the magnetization directions of the second magnetic pole portion 92 and the third magnetic pole portion 93 are along the thickness direction of the fixing member 80 (parallel to the thickness direction of the fixing member 80) (direction perpendicular to the width direction of the fixing member 80) in cross-sectional view, and the magnetization directions of the first magnetic pole portion 91 and the fourth magnetic pole portion 94 are along the width direction of the fixing member 80 (parallel to the width direction of the fixing member 80) (direction perpendicular to the thickness direction of the fixing member 80). If the magnetization directions are the above directions, the sputtering angle (angle θ) shown below is obtained.

[0178] As Figure 7 The sputtering angle (angle θ) in the magnet unit 75 of the first magnetron plasma unit 64 shown in FIG. 5 is, for example, 35 to 50 degrees, preferably 37 to 48 degrees, more preferably 39 to 46 degrees, and further preferably 40 to 45 degrees.

[0179] As Figure 7 The sputtering angle (angle θ) in the magnet unit 75 of the first magnetron plasma unit 64 shown in the figure is, for example, greater than 35 degrees, preferably greater than 37 degrees, more preferably greater than 39 degrees, and further preferably greater than 40 degrees. In addition, it is, for example, less than 50 degrees, preferably less than 48 degrees, more preferably less than 46 degrees, and further preferably less than 45 degrees.

[0180] It should be noted that the sputtering angle refers to the angle θ shown below. On the outer peripheral surface of the rotating target 74, the tangential direction component of the magnetic flux density is measured in one direction toward the circumferential direction of the rotating target. The angle θ formed by the line segment LS1 and the line segment LS2 is obtained. The line segment LS1 is a line segment connecting the point MAX_P corresponding to the maximum tangential direction component of the magnetic flux density and the center of the rotating target 74, and the line segment LS2 is a line segment connecting the point MIN_P corresponding to the minimum tangential direction component of the magnetic flux density and the center. The angle θ is obtained, for example, by simulation of the magnetic field using commercially available software.

[0181] Here, the tangential direction component of the magnetic flux density obtained by the above-mentioned simulation will be described.

[0182] like Figure 7 and Figure 8As shown, in the first unit 72, a tunnel-shaped first magnetic field MF1 (depicted by a plurality of points) is generated from the opposite side of the second magnetic pole portion 92 having an N pole toward the opposite side of the first magnetic pole portion 91 having an S pole. It should be noted that if the second magnetic pole portion 92 is an N pole and the first magnetic pole portion 91 is an S pole, the minimum magnetic flux density (that is, the strongest value of the magnetic field on the negative side, MIN_P) can be obtained by measuring the tangential direction component of the magnetic flux density in the circumferential direction of the rotating target 74 and in one direction from the first magnetic pole portion 91 toward the second magnetic pole portion 92.

[0183] In addition, a second magnetic field MF2 (depicted by a plurality of points) having a tunnel shape is generated from the opposite side of the third magnetic pole portion 93 having an N pole toward the opposite side of the fourth magnetic pole portion 94 having an S pole. If the third magnetic pole portion 93 is an N pole and the fourth magnetic pole portion 94 is an S pole, the maximum magnetic flux density (that is, the strongest value of the magnetic field on the positive side, MAX_P) can be obtained by measuring the tangential direction component of the magnetic flux density in the circumferential direction of the rotating target 74 and in one direction from the third magnetic pole portion 93 toward the fourth magnetic pole portion 94.

[0184] It should be noted that the point MAX_P corresponding to the maximum tangential direction component of the magnetic flux density and the point MIN_P corresponding to the minimum tangential direction component have the same meaning as the points corresponding to two maximum values ​​in the absolute value of the tangential direction component of the magnetic flux density.

[0185] The sputtering angle (angle θ) is an angle on the film forming roller 63 side of the angle formed by the above-mentioned two line segments LS1 and LS2 .

[0186] At once Figure 7 As for the sputtering angle in the magnet unit 75 of the first magnetron plasma unit 64 shown in the figure, on the radial outside of the rotating target 74, the distance in the circumferential direction between the plasma corresponding to the largest tangential direction component of the magnetic flux density and the plasma corresponding to the smallest tangential direction component of the magnetic flux density becomes greater.

[0187] on the other hand, Figure 8 The thickness direction length and width direction length of the first magnetic pole portion 91, the second magnetic pole portion 92, the third magnetic pole portion 93 and the fourth magnetic pole portion 94 in the magnet unit 75 of the second magnetron plasma unit 64 shown in FIG. 1 , that is, the ratio (D / L) of the separation distance D (the length of the side) between the opposite side and the fixed side to the length L of the opposite side is, for example, 1.2 to 6.0, preferably 1.3 to 6.0, more preferably 1.5 to 6.0, further preferably 1.6 to 6.0, and particularly preferably 1.7 to 6.0.

[0188] Figure 8The thickness direction length and width direction length of the first magnetic pole portion 91, the second magnetic pole portion 92, the third magnetic pole portion 93 and the fourth magnetic pole portion 94 in the magnet unit 75 of the second magnetron plasma unit 64 shown in FIG. 1 , that is, the ratio (D / L) of the separation distance D (the length of the side) between the opposite side and the fixed side to the length L of the opposite side is, for example, greater than 1.2, preferably greater than 1.3, more preferably greater than 1.5, further preferably greater than 1.6, particularly preferably greater than 1.7, and for example less than 6.0.

[0189] When the ratio (D / L) is in the above range, the sputtering angle (angle θ) shown below is obtained.

[0190] exist Figure 8 In the magnet unit 75 included in the second magnetron plasma unit 64 shown in FIG, the magnetization directions of the second magnetic pole portion 92 and the third magnetic pole portion 93 are inclined relative to the thickness direction and the width direction of the fixed member 80 in cross-sectional view, and the magnetization directions of the first magnetic pole portion 91 and the fourth magnetic pole portion 94 are along the width direction of the fixed member 80 (parallel to the width direction of the fixed member 80) (direction orthogonal to the thickness direction of the fixed member 80). It should be noted that the magnetization directions of the first magnetic pole portion 91 and the fourth magnetic pole portion 94 may also be inclined relative to the thickness direction and the width direction of the fixed member 80.

[0191] Specifically, the magnetization directions of the second magnetic pole portion 92 and the third magnetic pole portion 93 are inclined in directions intersecting with each other as they approach the film forming roller 63 in the thickness direction of the fixing member 80 .

[0192] It should be noted that when the magnetization directions of the first magnetic pole portion 91 and the fourth magnetic pole portion 94 are also inclined relative to the thickness direction and width direction of the fixed component 80, the respective magnetization directions of the first magnetic pole portion 91 and the fourth magnetic pole portion 94 are inclined in directions intersecting with each other as they move away from the film-forming roller 63 in the thickness direction of the fixed component 80.

[0193] By making the magnetization directions of the second magnetic pole portion 92 and the third magnetic pole portion 93 intersect each other, the magnetic flux on the surface of the rotating target 74 can be concentrated. As a result, the two tunnel-shaped magnetic fields approach each other and have a sputtering angle (angle θ) shown below. Specifically, Figure 8 The sputtering angle (angle θ) in the magnet unit 75 of the second magnetron plasma unit 64 shown in FIG. Figure 7 The sputtering angle (angle θ) in the magnet unit 75 included in the first magnetron plasma unit 64 shown in FIG. 7 is small.

[0194] As Figure 8The sputtering angle (angle θ) in the magnet unit 75 of the second magnetron plasma unit 64 shown in FIG. 1 is, for example, 10 to 35 degrees, preferably 15 to 34 degrees, more preferably 20 to 33 degrees, and further preferably 22 to 32 degrees.

[0195] As Figure 8 The sputtering angle (angle θ) in the magnet unit 75 of the second magnetron plasma unit 64 shown in the figure is, for example, greater than 10 degrees, preferably greater than 15 degrees, more preferably greater than 20 degrees, and further preferably greater than 22 degrees. In addition, it is, for example, less than 35 degrees, preferably less than 34 degrees, more preferably less than 33 degrees, and further preferably less than 32 degrees.

[0196] In addition, if the sputtering angle (angle θ) is within the above range, the distance in the circumferential direction between the plasma corresponding to the maximum tangential component of the magnetic flux density and the plasma corresponding to the minimum tangential component of the magnetic flux density on the radially outer side of the rotating target 74 becomes closer. Therefore, the area with a high density of electrons released from the rotating target 74 can be concentrated. In other words, the maximum magnetic flux density at point MAX_P can be made larger, and the density of the formed layer can be increased. In addition, if the sputtering angle (angle θ) is above the above lower limit, the magnetic flux density can be suppressed from becoming too low. In other words, the minimum magnetic flux density at point MIN_P can be made smaller, and plasma can be continuously generated.

[0197] Examples of materials for the first magnet 81 and the second magnet 82 include permanent magnets such as neodymium magnets.

[0198] like Figure 6 As shown, the second unit 73 includes a rotating target 74 that can rotate in the same direction as the rotation direction of the deposition roller 63 , and the above-mentioned magnet unit 75 .

[0199] The second unit 73 also has the same configuration as the first unit 72 .

[0200] <Primer layer forming step>

[0201] In the primer layer 3 forming step, specifically, the primer layer 3 is formed by forming the above-mentioned primer layer 3 material on one surface in the thickness direction of the transparent base film 2 (one surface in the thickness direction of the cured resin layer 22) by sputtering.

[0202] In the sputtering method, a sputtering film forming device such as the above-mentioned device Z that can implement the film forming process in a roll-to-roll manner is used. In the primer layer forming process, when a roll-to-roll sputtering film forming device is used, the transparent base film 2 as the working film W is moved from the delivery roller 52 to the winding roller 53, and the material of the primer layer 3 is formed on one surface of the transparent base film 2 in the thickness direction to form the primer layer 3. The travel speed of the working film W (transparent base film 2) is, for example, 0.5 to 10.0 m / min. It should be noted that in the primer layer forming process, a roll-to-roll sputtering film forming device is used. Figure 7 The first magnetron plasma unit 64 shown in FIG. 7 includes a magnet unit 75 .

[0203] It should be noted that in the sputtering method of the primer layer forming step, a sputtering film forming device having a film forming chamber can be used, or a sputtering film forming device such as Figure 5 The sputtering film forming apparatus shown includes a plurality of film forming chambers ( R1 to R4 ) arranged in sequence along a travel path of the working film W (transparent base film 2 ).

[0204] In the sputtering method, specifically, a sputtering gas (inert gas) is introduced into the film forming chamber R under vacuum conditions, and a negative voltage is applied to the target arranged on the outer peripheral surface of the rotating target 74 in the film forming chamber R. As a result, a glow discharge is generated, gas atoms are ionized, and the gas ions collide with the target surface at high speed, and the target material is ejected from the target surface, and the ejected target material is deposited on one surface in the thickness direction of the working film W (transparent base film 2). As the material of the target, for example, a sintered body of the material of the primer layer 3 described above is used.

[0205] As the sputtering gas, for example, argon, krypton, xenon and a mixed gas thereof can be cited, and argon is preferably cited. The sputtering method is preferably a reactive sputtering method. In the reactive sputtering method, for example, in addition to the sputtering gas, oxygen as a reactive gas is also introduced into the film forming chamber R.

[0206] The ultimate vacuum degree in the film forming chamber R before sputtering film formation is, for example, 1.5×10 -4 Below Pa.

[0207] In the reactive sputtering method, the ratio of the volume of oxygen introduced into the film forming chamber R to the total volume of the sputtering gas and oxygen (reactive gas) is, for example, 1 volume % to 30 volume %, preferably 3 volume % to 20 volume %, more preferably 5 volume % to 15 volume %, and further preferably 7 volume % to 12 volume %.

[0208] The film-forming temperature (temperature of the transparent base film 2 when the primer layer 3 is formed) is, for example, -50.0°C to 30.0°C, preferably -30.0°C to 20.0°C, more preferably -20.0°C to 10.0°C, and further preferably -15.0°C to 0.0°C.

[0209] The gas pressure in the film forming chamber R (the gas pressure in the film forming chamber when the sputtering gas and oxygen are introduced) is, for example, 0.01 Pa to 5.0 Pa, preferably 0.05 Pa to 1.0 Pa, more preferably 0.10 Pa to 0.50 Pa, and further preferably 0.15 Pa to 0.30 Pa.

[0210] As a power source for applying a voltage to the target, for example, a DC (Direct Current) power source, an AC (Alternating Current) power source, an MF (Middle Frequency) power source, and an RF (Radio Frequency) power source can be listed. As a power source, an MF power source and an AC power source can also be used in combination. As a power source, a MFAC power source can be preferably listed.

[0211] The horizontal magnetic field intensity on the target is, for example, 10 mT to 100 mT.

[0212] As described above, the primer layer 3 is formed on one surface in the thickness direction of the transparent base film 2 .

[0213] <Alternating laminate forming step>

[0214] In the alternating stacked body forming step, specifically, an alternating stacked body composed of niobium oxide layers 41 and silicon oxide layers 42 is formed by sputtering on one surface in the thickness direction of the primer layer 3. Specifically, a niobium oxide layer 41a (first layer), a silicon oxide layer 42a (second layer), a niobium oxide layer 41b (third layer), and a silicon oxide layer 42b (fourth layer) are sequentially formed on one surface in the thickness direction of the primer layer 3, thereby forming an alternating stacked body.

[0215] In the sputtering method, a sputtering film forming device such as the above-mentioned device Z that can implement a film forming process in a roll-to-roll manner is used. In the alternating stack formation process, when a roll-to-roll sputtering film forming device is used, a transparent base film 2 having a primer layer 3 as a working film W is moved from a delivery roller 52 to a winding roller 53, and the materials of the alternating stack (specifically, niobium and silicon) are sequentially formed on one surface in the thickness direction of the primer layer 3 to form an alternating stack. The travel speed of the working film W (the transparent base film 2 having the primer layer 3) is, for example, 0.5 to 10.0 m / min. It should be noted that in the alternating stack formation process, a roll-to-roll sputtering film forming device is used. Figure 8 The second magnetron plasma unit 64 shown in FIG. 7 includes a magnet unit 75 .

[0216] It should be noted that in the sputtering method of the alternately stacked body forming step, the following is used: Figure 5The sputtering film forming apparatus shown includes a plurality of film forming chambers ( R1 to R4 ) sequentially arranged along a travel path of the working film W (transparent base film 2 including the primer layer 3 ), and sequentially forms the first to fourth layers.

[0217] In the sputtering method, specifically, a sputtering gas (inert gas) is introduced into the film forming chamber R under vacuum conditions, and a negative voltage is applied to the target arranged on the outer peripheral surface of the rotating target 74 in the film forming chamber R. As a result, a glow discharge is generated, gas atoms are ionized, and the gas ions collide with the target surface at high speed, and the target material is ejected from the target surface, and the ejected target material is sequentially deposited in the thickness direction. As the material of the target, niobium is used for the first and third layers, and silicon is used for the second and fourth layers.

[0218] As the sputtering gas, for example, argon, krypton, xenon and a mixed gas thereof can be cited, and argon is preferably cited. The sputtering method is preferably a reactive sputtering method. In the reactive sputtering method, for example, in addition to the sputtering gas, oxygen as a reactive gas is also introduced into the film forming chamber R.

[0219] In the reactive sputtering method when forming the first layer and the third layer, the ratio of the volume of oxygen introduced into the film forming chamber (R1 and R3) to the total volume of the sputtering gas and oxygen (reactive gas) is, for example, 0.5 volume % to 20 volume %, preferably 1 volume % to 10 volume %, more preferably 2 volume % to 8 volume %, and further preferably 3 volume % to 6 volume %.

[0220] In the reactive sputtering method when forming the second layer and the fourth layer, the ratio of the volume of oxygen introduced into the film forming chamber (R2 and R4) to the total volume of the sputtering gas and oxygen (reactive gas) is, for example, 5 volume % to 50 volume %, preferably 10 volume % to 40 volume %, more preferably 15 volume % to 30 volume %, and further preferably 20 volume % to 25 volume %.

[0221] The gas pressure in the film forming chamber R (the gas pressure in the film forming chamber when the sputtering gas and oxygen are introduced) is, for example, 0.01 Pa to 5.0 Pa, preferably 0.05 Pa to 3.0 Pa, more preferably 0.10 Pa to 1.0 Pa, and further preferably 0.15 Pa to 0.80 Pa.

[0222] It should be noted that the ultimate vacuum degree in the film forming chamber R before sputtering film formation, the film forming temperature (the temperature of the transparent substrate film 2 when forming each layer), the power supply for applying voltage to the target, and the horizontal magnetic field strength on the target are the same as those in the above-mentioned primer layer formation process.

[0223] As described above, an alternately laminated body is formed on one surface in the thickness direction of the primer layer 3 .

[0224] <Antifouling layer forming process>

[0225] In the antifouling layer forming step, specifically, the antifouling layer 43 is formed on one surface of the alternately laminated body in the thickness direction by dry coating. Examples of dry coating methods include vacuum evaporation, sputtering, and CVD (Chemical Vapor Deposition), and vacuum evaporation is preferably used.

[0226] In the vacuum deposition method, the material of the antifouling layer 43 is dried and the solidified material is used as a deposition source.

[0227] The vapor deposition temperature is, for example, 150°C to 500°C, or preferably 200°C to 300°C.

[0228] In this way, the antifouling layer 43 is formed on one surface in the thickness direction of the alternately stacked body. In other words, the barrier layer 4 is formed on one surface in the thickness direction of the primer layer 3. It should be noted that the barrier layer 4 includes, in order toward one side in the thickness direction: a niobium oxide layer 41a (first layer), a silicon oxide layer 42a (second layer), a niobium oxide layer 41b (third layer), a silicon oxide layer 42b (fourth layer), and the antifouling layer 43.

[0229] The barrier film 1 is manufactured in the above-mentioned manner.

[0230] 3. Polarizing plate with barrier film

[0231] Reference Figure 3 , one embodiment of the polarizing plate with a barrier film of the present invention is described.

[0232] like Figure 3 As shown, the polarizing plate 100 with a barrier film includes a barrier film 1 and a polarizing plate 10 disposed on the other side in the thickness direction of the barrier film 1 .

[0233] <Polarizing plate>

[0234] like Figure 3 As shown, the polarizing plate 10 includes, for example, a protective film 11 and a polarizing plate 12. It should be noted that the structure of the polarizing plate 10 is not limited thereto. Specifically, the polarizing plate 10 may include the protective film 11 on both sides of the polarizing plate 12 in the thickness direction on one side and the other side, or may not include the protective film on both sides, or may further include other functional layers (such as a phase difference layer, a conductive layer, and a resin substrate).

[0235] [Protective film]

[0236] As the protective film 11, for example, a resin film can be cited. As the material of the resin film, for example, acrylic resin, polycarbonate resin, polyester resin, cycloolefin resin and olefin resin can be cited, and acrylic resin can be preferably cited. The acrylic resin preferably contains a modified skeleton. As the modified skeleton, for example, a lactone ring structure, a maleic anhydride skeleton, an acrylonitrile skeleton, a styrene skeleton, etc. can be cited. It should be noted that (meth) acrylic resin refers to acrylic resin and / or methacrylic resin.

[0237] The moisture permeability of the protective film 11 is, for example, 0 g / m 2 / 24h~1000g / m 2 / 24h, preferably 10g / m 2 / 24h~500g / m 2 / 24h, more preferably 30g / m 2 / 24h~300g / m 2 / 24h, more preferably 50g / m 2 / 24h~200g / m 2 / 24h.

[0238] The moisture permeability of the protective film 11 is, for example, 0 g / m 2 / 24h or more, preferably 10g / m 2 / 24h or more, more preferably 30g / m 2 / 24h or more, more preferably 50g / m 2 / 24h or more, for example, 1000g / m 2 / 24h or less, preferably 500g / m 2 / 24h or less, more preferably 300g / m 2 / 24h or less, more preferably 200g / m 2 / 24h or less.

[0239] When the moisture permeability of the protective film 11 is within the above range, discoloration of the polarizing plate under heating and humidification conditions can be further suppressed.

[0240] The thickness of the protective film 11 is, for example, 1 μm to 300 μm, preferably 10 μm to 100 μm, and more preferably 20 μm to 80 μm.

[0241] The thickness of the protective film 11 is, for example, 1 μm or more, preferably 10 μm or more, more preferably 20 μm or more, and is, for example, 300 μm or less, preferably 100 μm or less, more preferably 80 μm or less.

[0242] [Polarizing plate]

[0243] The polarizing plate 12 is, for example, a resin coating film containing a dichroic substance. The resin coating film will be described in detail later, and the resin coating film is formed by coating a resin on one side of the resin substrate 13 .

[0244] The resin coating film is not particularly limited, and examples thereof include a coating film of a polyvinyl alcohol (PVA) resin.

[0245] As the PVA resin, for example, polyvinyl alcohol and ethylene-vinyl alcohol copolymer can be listed. Polyvinyl alcohol is obtained by saponifying polyvinyl acetate. Ethylene-vinyl alcohol copolymer is obtained by saponifying ethylene-vinyl acetate copolymer. In addition, polyvinyl alcohol can be a derivative of polyvinyl alcohol. As the derivative of polyvinyl alcohol, for example, cation-modified polyvinyl alcohol, anion-modified polyvinyl alcohol, silanol-modified polyvinyl alcohol and acetoacetyl-modified polyvinyl alcohol can be listed.

[0246] The PVA resin may be used alone or in combination of two or more kinds. Preferably, polyvinyl alcohol and acetoacetyl-modified polyvinyl alcohol are used in combination.

[0247] The saponification degree of the PVA resin is, for example, 85 mol % to 100 mol %, preferably 95.0 mol % to 99.95 mol %, and more preferably 99.0 mol % to 99.93 mol %. The saponification degree can be determined in accordance with JIS K6726-1994.

[0248] When the saponification degree of the PVA resin is within the above range, a polarizing plate having excellent durability can be obtained.

[0249] The average degree of polymerization of the PVA resin is, for example, 1000 to 10000, preferably 1200 to 4500, and more preferably 1500 to 4300. The average degree of polymerization can be determined in accordance with JIS K6726-1994.

[0250] Examples of the dichroic substance contained in the resin coating film include iodine and organic dyes, and preferably iodine. The dichroic substance may be used alone or in combination of two or more.

[0251] The polarizer 12 may be obtained by dyeing a PVA resin coating film with iodine and stretching (eg, uniaxially stretching). Although the details will be described later, the resin substrate 13 is coated with the PVA resin and then dyed and stretched.

[0252] The thickness of the polarizer 12 is, for example, 1 μm to 20 μm, preferably 2 μm to 15 μm, and more preferably 3 μm to 10 μm.

[0253] The thickness of the polarizer 12 is, for example, 1 μm or more, preferably 2 μm or more, more preferably 3 μm or more, and, for example, 20 μm or less, preferably 15 μm or less, more preferably 10 μm or less.

[0254] When the thickness of the polarizing plate 12 is within the above range, the polarizing plate with a barrier film can be made thinner and reliability during humidification and heating can be improved.

[0255] The polarizing plate 12 shows absorption dichroism at any wavelength of, for example, 380 nm to 780 nm. The single transmittance of the polarizing plate 12 is, for example, 40.0% to 50.0%, preferably 41.0% to 48.0%, and more preferably 42.0% to 45.0%.

[0256] The single transmittance of the polarizing plate 12 is, for example, 40.0% or more, preferably 41.0% or more, more preferably 42.0% or more, and is, for example, 50.0% or less, preferably 48.0% or less, more preferably 45.0% or less.

[0257] The degree of polarization of the polarizing plate is, for example, 97.0% or more, preferably 99.0% or more, and more preferably 99.9% or more.

[0258] [Other functional layers]

[0259] As other functional layers, for example, phase difference layers, conductive layers, and transparent resins can be listed. The type, number, combination, configuration position, and characteristics (such as refractive index characteristics, in-plane phase difference, thickness direction phase difference, and optical characteristics such as Nz coefficient) of other functional layers can be appropriately set according to the purpose.

[0260] As the phase difference layer, for example, a resin layer having a refractive index characteristic of nx>ny>nz and a resin layer having a refractive index characteristic of nz>nx>ny can be listed. As the material of such a phase difference layer, for example, the same resin as the material of the protective film 11 can be listed, and preferably, cycloolefin resin and olefin resin can be listed.

[0261] Although not shown in the figure, the polarizing plate 10 preferably has a phase difference layer on the surface opposite to the surface of the polarizer 12 in contact with the protective film 11. Specifically, although not shown in the figure, in the polarizing plate 10, the surface of the polarizer 12 on the opposite side to the protective film 11 has a first phase difference layer having a refractive index characteristic of nx>ny>nz, and the surface of the first phase difference layer on the opposite side to the polarizer 12 has a second phase difference layer having a refractive index characteristic of nz>nx>ny. It should be noted that the first phase difference layer can take into account the protection of the surface of the polarizer 12 on the opposite side to the surface in contact with the protective film 11. In the case of providing a phase difference layer, the angle between the slow axis of the phase difference layer (if present) and the absorption axis of the polarizer can be appropriately set according to the purpose, the in-plane phase difference of the phase difference layer, the thickness direction phase difference, the refractive index characteristics, etc.

[0262] As the conductive layer, for example, there can be mentioned a metal oxide layer formed of the same material as the above-mentioned primer layer 3. By providing the conductive layer, the polarizing plate with a barrier film is preferably used for an internal touch panel type input display device.

[0263] In addition, other functional layers may be attached to the polarizing plate 12 via an adhesive described later.

[0264] The thickness of the polarizing plate 10 is, for example, 10 μm to 1000 μm, preferably 30 μm to 500 μm, and more preferably 40 μm to 300 μm.

[0265] The thickness of the polarizing plate 10 is, for example, 10 μm or more, preferably 30 μm or more, more preferably 40 μm or more, and is, for example, 1000 μm or less, preferably 500 μm or less, more preferably 300 μm or less.

[0266] The water content of the polarizing plate 10 is, for example, 0.5 mass % to 1.5 mass %, preferably 0.6 mass % to 1.5 mass %, and more preferably 0.8 mass % to 1.5 mass %.

[0267] The water content of the polarizing plate 10 is, for example, 0.5 mass % or more, preferably 0.6 mass % or more, more preferably 0.8 mass % or more, and, for example, 1.5 mass % or less.

[0268] The moisture content of the polarizing plate 10 having a polarizer 12 formed by a coating film of a resin is higher than that of the polarizing plate having a polarizer formed by a resin film (such as a PVA film). By making the polarizing plate 10 have such a high moisture content, the hygroscopic expansion of the polarizing plate 10 under heating and humidification conditions can be significantly suppressed. As a result, the dimensional change of the polarizing plate 10 under heating and humidification conditions (especially the dimensional change in the absorption axis direction of the polarizing plate) is suppressed. However, the discoloration of the polarizing plate 10 under heating and humidification conditions becomes easy to occur. Therefore, it is necessary to suppress the discoloration of the polarizing plate 10 under heating and humidification conditions by having a barrier film 1.

[0269] The thickness of the polarizing plate 100 with a barrier film is, for example, 10 μm to 1000 μm, preferably 30 μm to 500 μm, and more preferably 50 μm to 300 μm.

[0270] The thickness of the polarizing plate 100 with a barrier film is, for example, 10 μm or more, preferably 30 μm or more, more preferably 50 μm or more, and, for example, 1000 μm or less, preferably 500 μm or less, more preferably 300 μm or less.

[0271] The moisture permeability of the polarizing plate 100 with a barrier film under the test conditions of a temperature of 40° C. and a humidity of 90% RH is, for example, 0.00 g / m 2 ·Day~100g / m 2 day, preferably 0.00g / m 2 ·Day~10g / m 2 day, more preferably 0.00 g / m 2 ·day~1.0g / m 2 day, more preferably 0.00 g / m 2 ·day~0.10g / m 2 day, particularly preferably 0.00 g / m 2 ·day~0.05g / m 2 day, the most preferred is 0.00 g / m 2 ·day~0.03g / m 2 ·day.

[0272] The moisture permeability of the polarizing plate 100 with a barrier film under the test conditions of a temperature of 40° C. and a humidity of 90% RH is, for example, 0.00 g / m 2 day or more, for example, 100 g / m 2 Less than one day, preferably 10g / m 2 ·Day or less, more preferably 1.0g / m 2 ·day or less, more preferably 0.10g / m 2·day or less, particularly preferably 0.05g / m 2 Less than 1 day, the most preferred is 0.03 g / m 2 ·Day or less.

[0273] The water vapor permeability of the polarizing plate 100 with a barrier film under the test conditions of a temperature of 40° C. and a humidity of 90% RH can be measured using a water vapor permeability measuring apparatus.

[0274] Chromaticity change Δb of transmitted light of the polarizing plate with barrier film under heating and humidification conditions of 60°C, 90% RH, and 240 hours * For example, it is 0.00 to 1.00, preferably 0.05 to 0.50, more preferably 0.10 to 0.30, and further preferably 0.10 to 0.28.

[0275] Chromaticity change Δb of transmitted light of the polarizing plate with barrier film under heating and humidification conditions of 60°C, 90% RH, and 240 hours * For example, it is 0.00 or more, preferably 0.05 or more, more preferably 0.10 or more, and for example, it is 1.00 or less, preferably 0.50 or less, more preferably 0.30 or less, and further preferably 0.28 or less.

[0276] Chromaticity change Δb of transmitted light of the polarizing plate with barrier film under heating and humidification conditions of 60°C, 90% RH, and 500 hours * For example, it is 0.00 to 2.00, preferably 0.05 to 1.00, more preferably 0.10 to 0.80, and further preferably 0.10 to 0.50.

[0277] Chromaticity change Δb of transmitted light of the polarizing plate with barrier film under heating and humidification conditions of 60°C, 90% RH, and 500 hours * For example, it is 0.00 or more, preferably 0.05 or more, more preferably 0.10 or more, and for example, it is 2.00 or less, preferably 1.00 or less, more preferably 0.80 or less, and further preferably 0.50 or less.

[0278] It should be noted that the change in chromaticity of the transmitted light Δb * It can be determined by the method described in the examples described later.

[0279] 4. Method for manufacturing polarizing plate with barrier film

[0280] Reference Figure 4 (A)~ Figure 4 (E) The method for producing the polarizing plate with a barrier film of the present invention is described.

[0281] The method for manufacturing the polarizing plate 100 with a barrier film includes, for example, a step of preparing a resin substrate 13 ( Figure 4 (A)); forming a polyvinyl alcohol resin coating film (polarizer 12) on a resin substrate 13; step ( Figure 4 (B)); a step of attaching a protective film 11 to the polarizer 12 via an adhesive layer ( Figure 4 (C)); the step of removing the resin substrate 13 ( Figure 4 and a step of attaching the barrier film 1 to the surface of the protective film 11 via an adhesive ( Figure 4 (E)).

[0282] <Preparation process>

[0283] In the preparation process, Figure 4 As shown in (A), a resin base material 13 is prepared.

[0284] The resin substrate 13 has a film shape, for example. The resin of the resin substrate 13 is not particularly limited, and examples thereof include the same resins as those of the transparent resin film 21 , preferably polyester resins, and more preferably polyethylene terephthalate and copolymer resins thereof.

[0285] The thickness of the resin base material 13 is, for example, 10 μm to 300 μm, preferably 30 μm to 200 μm, and more preferably 50 μm to 150 μm.

[0286] The thickness of the resin base material 13 is, for example, 10 μm or more, preferably 30 μm or more, more preferably 50 μm or more, and is, for example, 300 μm or less, preferably 200 μm or less, more preferably 150 μm or less.

[0287] One side of the resin substrate 13 (the side on which the polarizer 12 is formed) may be subjected to surface modification treatment such as corona treatment, plasma treatment, flame treatment, ozone treatment, primer treatment, glow treatment, saponification treatment, and treatment with a coupling agent.

[0288] <Polarizing plate forming process>

[0289] In the polarizing plate forming process, Figure 4 As shown in (B), the polarizing plate 12 is formed on one surface (the surface treated surface when the surface modification treatment is performed) of the resin substrate 13 .

[0290] Specifically, an aqueous solution containing a polyvinyl alcohol resin is applied to one surface of the resin substrate 13. Then, the solution is dried to form a coating film of the polyvinyl alcohol resin.

[0291] Next, the resin substrate having the coating film of the polyvinyl alcohol resin (hereinafter referred to as a substrate with a PVA film) is dyed with iodine and stretched (for example, uniaxially stretched).

[0292] For dyeing with iodine, for example, the substrate with the PVA film is immersed in an iodine aqueous solution.

[0293] The stretching includes, for example, immersing the laminate in a boric acid aqueous solution and stretching the laminate in mid-air at a high temperature (eg, 95° C. or higher) before stretching in the boric acid aqueous solution.

[0294] The stretching ratio of the stretching is, for example, 3 to 7 times. It should be noted that the stretching may be performed after dyeing or while dyeing. In addition, dyeing may be performed after stretching.

[0295] Furthermore, the substrate with the PVA film is subjected to insolubilization treatment, swelling treatment, cross-linking treatment, washing treatment, drying treatment, and the like as necessary.

[0296] The polarizing plate 12 is formed on one surface of the resin substrate 13 in the above-described manner.

[0297] <Protective film attaching process>

[0298] In the protective film attachment process, Figure 4 As shown in (C), the protective film 11 is attached to the surface of the polarizer 12 on the opposite side of the surface in contact with the resin substrate 13 via an adhesive layer (not shown).

[0299] Specifically, an adhesive is applied to the surface (exposed surface) of the polarizer 12 opposite to the surface in contact with the resin substrate 13, and the protective film 11 is attached. Then, the protective film 11 is heated and irradiated with ultraviolet rays to cure the adhesive.

[0300] The adhesive is not particularly limited as long as it is an adhesive commonly used in the optical field. Examples of the adhesive include PVA adhesives and activated energy ray-curable adhesives, and preferably, acrylic adhesives are used.

[0301] The thickness of the adhesive layer (adhesive after curing) between the polarizer 12 and the protective film 11 is, for example, 0.1 μm to 5.0 μm, or preferably 0.5 μm to 3.0 μm.

[0302] The thickness of the adhesive layer (adhesive after curing) between the polarizer 12 and the protective film 11 is, for example, 0.1 μm or more, preferably 0.5 μm or more, and, for example, 5.0 μm or less, preferably 3.0 μm or less.

[0303] If the adhesive is an acrylic adhesive, it is cured by ultraviolet irradiation. As a light source for ultraviolet irradiation, for example, a metal halide lamp can be cited. The cumulative irradiation light amount of ultraviolet rays is, for example, 500 mJ / cm 2 ~2000mJ / cm 2 .

[0304] As described above, the protective film 11 is attached to the surface of the polarizing plate 12 opposite to the surface in contact with the resin substrate 13 .

[0305] <Resin base material removal process>

[0306] In the resin matrix removal process, such as Figure 4 As shown in (D), the resin base material 13 is removed (peeled off).

[0307] As described above, the polarizing plate 10 including the polarizer 12 and the protective film 11 is obtained.

[0308] In addition, the resin substrate 13 may not be removed but may be used as another functional layer. Specifically, the polarizing plate 10 including the resin substrate 13 , the polarizer 12 , and the protective film 11 may be provided.

[0309] <Barrier film attaching process>

[0310] In the barrier film attachment process, Figure 4 As shown in (E), the barrier film 1 is attached to the surface of the protective film 11 on the opposite side of the surface in contact with the polarizing plate 12 via an adhesive.

[0311] The adhesive is not particularly limited as long as it is an adhesive commonly used in the optical field. Examples of the adhesive include adhesives used when bonding the protective film 11 and the polarizing plate 12 , and preferably, an acrylic adhesive is used.

[0312] The thickness of the adhesive layer (adhesive after curing) between the polarizing plate 10 and the barrier film 1 is, for example, 1 μm to 50 μm, preferably 5 μm to 40 μm, and more preferably 10 μm to 30 μm.

[0313] The thickness of the adhesive layer (cured adhesive) between the polarizing plate 10 and the barrier film 1 is, for example, 1 μm or more, preferably 5 μm or more, more preferably 10 μm or more, and, for example, 50 μm or less, preferably 40 μm or less, more preferably 30 μm or less.

[0314] 5. Modifications

[0315] <Modification examples of barrier films>

[0316] exist Figure 1In the barrier film 1 , the barrier layer 4 includes, in order toward one side in the thickness direction: an alternately stacked body consisting of a niobium oxide layer 41 a , a silicon oxide layer 42 a , a niobium oxide layer 41 b , and a silicon oxide layer 42 b ; and an antifouling layer 43 , but the present invention is not limited thereto.

[0317] exist Fig. 9 In the barrier film 1 used in the polarizing plate 100 with a barrier film shown in , the barrier layer 4 is formed of a silicon oxide layer 42 (second layer) and an antifouling layer 43 disposed on one surface in the thickness direction of the silicon oxide layer 42. Although not shown in the figure, the barrier layer 4 may be formed of an alternating laminated body formed of a niobium oxide layer 41 (first layer) and a silicon oxide layer 42 (second layer) and an antifouling layer 43 disposed on one surface in the thickness direction of the alternating laminated body.

[0318] That is, the barrier layer is not particularly limited as long as it includes at least one silicon oxide layer 42 and an antifouling layer 43 disposed on one side in the thickness direction of the silicon oxide layer 42. Specifically, the number and order of stacking the niobium oxide layer 41 and the silicon oxide layer 42 are not particularly limited.

[0319] <Method for producing a modified example of a barrier film>

[0320] Reference Fig.10 (A)~ Fig.10 (E), yes Fig. 9 A method for producing the barrier film 1 used for the polarizing plate with a barrier film 100 shown in FIG. 1 is described below.

[0321] Fig. 9 The method for manufacturing the barrier film 1 used in the polarizing plate with a barrier film 100 shown in FIG. 1 includes, for example, a preparation step ( Fig.10 (A)), preparing a transparent resin film 21; curing resin layer forming step ( Fig.10 (B)), forming a cured resin layer 22 on the transparent resin film 21; primer layer forming step ( Fig.10 (C)), forming a primer layer 3 on the cured resin layer 22; silicon oxide layer forming step ( Fig.10 (D)), forming a silicon oxide layer 42 on the primer layer 3; and an antifouling layer forming step ( Fig.10 (E)), an antifouling layer 43 is formed on the silicon oxide layer 42. It should be noted that the primer layer forming step and the silicon oxide layer forming step are performed using the following method: Figure 5 The device Z shown is implemented sequentially.

[0322] It should be noted that in the following description, Figure 2 The method for producing the barrier film 1 shown in FIG.

[0323] <Silicon oxide layer forming step>

[0324] In the silicon oxide layer forming step, specifically, the silicon oxide layer 42 is formed on one surface in the thickness direction of the primer layer 3 by sputtering.

[0325] In the sputtering method, a sputtering film forming device such as the above-mentioned device Z that can implement the film forming process in a roll-to-roll manner is used. In the silicon oxide layer forming step, when a roll-to-roll sputtering film forming device is used, the transparent base film 2 having a primer layer 3 as a working film W is moved from a delivery roller 52 to a winding roller 53, and the material of the silicon oxide layer (specifically silicon) is formed on one surface in the thickness direction of the primer layer 3 to form a silicon oxide layer 42. The travel speed of the working film W (the transparent base film 2 having the primer layer 3) is, for example, 0.5 to 10.0 m / min. It should be noted that in the silicon oxide layer forming step, a roll-to-roll sputtering film forming device is used. Figure 8 The second magnetron plasma unit 64 shown in FIG. 7 includes a magnet unit 75 .

[0326] It should be noted that in the sputtering method of the silicon oxide layer forming step, a sputtering film forming device having a film forming chamber R can be used, or a sputtering film forming device such as Figure 5 The sputtering film forming apparatus shown in FIG. 1 is provided with a plurality of film forming chambers R arranged in sequence along the path of travel of the working film W (the transparent base film 2 having the primer layer 3). Figure 5 In the case of the device Z shown, film formation can be performed in only one film forming chamber (e.g., R2). It should be noted that, in the case of forming an alternating stack of niobium oxide layers 41 (first layer) and silicon oxide layers 42 (second layer), film formation can be performed in two film forming chambers (e.g., R1 and R2).

[0327] In the sputtering method, specifically, a sputtering gas (inert gas) is introduced into the film forming chamber R under vacuum conditions, and a negative voltage is applied to a target arranged on the outer peripheral surface of a rotating target 74 in the film forming chamber R. As a result, a glow discharge is generated, gas atoms are ionized, and the gas ions collide with the target surface at high speed, and the target material is ejected from the target surface, and the ejected target material is sequentially deposited in the thickness direction. Silicon is used as the material of the target.

[0328] As the sputtering conditions, Figure 2 The silicon oxide layer 42a (second layer) in the method for manufacturing the barrier film 1 shown in is the same.

[0329] As described above, the silicon oxide layer 42 is formed on one surface in the thickness direction of the primer layer 3 .

[0330] Example

[0331] The following examples, comparative examples and reference examples are shown to further specifically describe the present invention. It should be noted that the present invention is not limited to any examples, comparative examples and reference examples. In addition, the specific numerical values ​​such as the mixing ratio (containing ratio), physical property values, parameters used in the following description can be replaced by the upper limit (defined as "below", "less than") or lower limit (defined as "above", "exceeding") of the corresponding recordings of the mixing ratio (containing ratio), physical property values, parameters, etc. recorded in the above-mentioned "specific embodiments" and corresponding to them.

[0332] Example 1

[0333] <Production of protective film>

[0334] Methyl methacrylate (MMA), methyl 2-(hydroxymethyl)acrylate (MHMA), toluene, and polystyrene were placed in a reactor equipped with a stirring device, a temperature sensor, a cooling tube, and a nitrogen inlet tube, and a cyclization condensation reaction and degassing were carried out in an extruder at 250°C to obtain transparent acrylic resin particles containing lactone rings. The obtained particles were put into a single-screw extruder, melt-mixed, and formed into a film through a T-die. The obtained extruded film was simultaneously biaxially stretched to 2 times in the length direction and the width direction at a stretching temperature of 160°C. The thickness of the obtained film was 40μm. The resin composition ratio of the obtained film was confirmed by NMR, and the result was that MMA was 76%, lactone ring was 19%, and styrene was 5%.

[0335] <Production of polarizing plate>

[0336] A long amorphous isophthalic acid copolymer polyethylene terephthalate film (water absorption: 0.75%, glass transition temperature: 75°C, thickness: 100 μm) was prepared as a resin substrate. Next, one side of the resin substrate was subjected to corona treatment. An aqueous solution containing polyvinyl alcohol (polymerization degree: 4200, saponification degree: 99.2 mol%) and acetoacetyl-modified polyvinyl alcohol (trade name: GOHSEFIMER Z200, polymerization degree: 1200, acetoacetyl modification degree: 4.6%, saponification degree: 99.0 mol% or more, manufactured by Nippon Synthetic Chemical Industry Co., Ltd.) in a ratio of 9:1 was applied to the corona-treated surface at 25°C and dried to form a coating film (PVA film) of polyvinyl alcohol resin with a thickness of 11 μm, thereby obtaining a substrate with a PVA film.

[0337] Then, the substrate with the PVA film is subjected to free-end uniaxial stretching to 2.0 times in the longitudinal direction (long dimension direction) between rollers with different circumferential speeds in an oven at 120°C (auxiliary stretching in the air). Next, the substrate with the PVA film is immersed in an insolubilization bath (a boric acid aqueous solution obtained by adding 4 parts by mass of boric acid to 100 parts by mass of water) at a liquid temperature of 30°C for 30 seconds (insolubilization treatment). Next, in a dyeing bath at a liquid temperature of 30°C, the iodine concentration and the immersion time are adjusted so that the polarizing plate has a specified transmittance while being immersed. Specifically, it is immersed in an iodine aqueous solution obtained by adding 0.2 parts by mass of iodine to 100 parts by mass of water and 1.5 parts by mass of potassium iodide for 60 seconds (dyeing treatment). Next, it is immersed in a cross-linking bath (a boric acid aqueous solution obtained by adding 3 parts by mass of potassium iodide to 100 parts by mass of water) at a liquid temperature of 30°C for 30 seconds (cross-linking treatment). Then, the substrate with the PVA film was immersed in a boric acid aqueous solution (an aqueous solution obtained by adding 4 parts by mass of boric acid to 100 parts by mass of water and 5 parts by mass of potassium iodide) at a liquid temperature of 70°C, and uniaxially stretched (underwater stretching) in the longitudinal direction (long dimension direction) between rollers with different peripheral speeds so that the total stretching ratio was 5.5 times. Then, the substrate with the PVA film was immersed in a cleaning bath (an aqueous solution obtained by adding 4 parts by mass of potassium iodide to 100 parts by mass of water) at a liquid temperature of 30°C (cleaning treatment).

[0338] Next, the adhesive shown below was applied to the surface of the polyvinyl alcohol resin coating film (polarizer) of the substrate with the PVA film so that the thickness of the adhesive layer after curing was 1.0 μm, and the methacrylic resin film (thickness: 40 μm, moisture permeability: 100 g / m 2 / 24h) as a protective film, using an IR heater to heat to 50 ° C from the methacrylic resin film side, irradiating ultraviolet rays under the following conditions to cure the adhesive. Then, the resin substrate was peeled off from the polarizer to obtain a polarizing plate (a polarizing plate with a polarizer and a protective film). It should be noted that the thickness of the polarizer is 5 μm and the monomer transmittance is 42.3%. In addition, the moisture content of the obtained polarizing plate is 1.0 mass%.

[0339] (Adhesive composition)

[0340] 40 parts by mass of N-hydroxyethyl acrylamide (HEAA), 60 parts by mass of acryloylmorpholine (ACMO), and 3 parts by mass of a photoinitiator "IRGACURE 819" (manufactured by BASF) were mixed to prepare an adhesive having a viscosity of 40 mPa·S before curing.

[0341] (UV conditions)

[0342] Ultraviolet light (gallium-enclosed metal halide lamp, irradiation device: LightHAMMER10 manufactured by FusionUVSystems, Inc., valve: V valve, peak illuminance: 1600 mW / cm 2 , cumulative irradiation 1000mJ / cm 2 (wavelength 380 to 440 nm)) as active energy rays. The illuminance of ultraviolet rays was measured using the Sola-Check system manufactured by Solatell.

[0343] <Production of barrier film>

[0344] A barrier film was produced as follows.

[0345] [Production of transparent substrate film]

[0346] The acrylic monomer composition containing nano-silica particles (trade name: NC035HS, solid content concentration: 60% by mass, made by Arakawa Chemical Industries) 83 parts by mass, ultraviolet curing multifunctional urethane acrylate (trade name: BEAMSET 580, solid content concentration: 70% by mass, made by Arakawa Chemical Industries) 17 parts by mass, photopolymerization initiator (trade name: OMNIRAD127D, made by IGM Resins) 1.5 parts by mass, leveling agent (trade name: LE303, solid content concentration: 40% by mass, made by Kyoeisha Chemical Co., Ltd.) 0.15 parts by mass and butyl acetate were mixed to prepare a curable resin composition with a solid content concentration of 42% by mass. The composition was applied to one side of a 100 μm thick triacetyl cellulose film (trade name: FUJITAC, made by FUJI FILM) in a manner of 5 μm thickness after drying, and dried at 80°C for 3 minutes. Then, a high-pressure mercury lamp was used to irradiate a cumulative light amount of 200 mJ / cm 2 The coating layer is cured by ultraviolet light to form a cured resin layer. Thus, a transparent base film having a cured resin layer on the transparent resin film is obtained.

[0347] [Formation of primer layer]

[0348] Next, a 4 nm thick ITO layer (primer layer) was formed on one side of the transparent substrate film in the thickness direction (one side of the cured resin layer in the thickness direction) by reactive sputtering. The primer layer was formed using the following method: Figure 5 The roll-to-roll sputtering film forming device Z (magnetron sputtering film forming device Z) shown in the figure. It should be noted that the sputtering film forming device Z has a film forming chamber that can make the working film (transparent substrate film) move in a roll-to-roll manner and implement the film forming process. In addition, the sputtering film forming device Z used for forming the primer layer has Figure 7The details of the magnet unit and sputtering film forming conditions of the first magnetron plasma unit used for forming the primer layer are shown below.

[0349] In the magnet unit of the first magnetron plasma unit, the first to fourth magnetic pole portions are used, the length L of the opposite side is 13 mm, and the separation distance D between the opposite side and the fixed side (the length of the side) is 13 mm. It should be noted that the second magnetic pole portion and the third magnetic pole portion are set as N poles, and the first magnetic pole portion and the fourth magnetic pole portion are set as S poles. In addition, the magnetization direction of the second magnetic pole portion and the third magnetic pole portion is set to a direction orthogonal to the width direction of the fixed component, and the magnetization direction of the first magnetic pole portion and the fourth magnetic pole portion is set to a direction along the width direction of the fixed component (parallel to the width direction of the fixed component). By adopting such a structure, the sputtering angle (angle θ) can be set to about 42 degrees.

[0350] The vacuum was exhausted until the ultimate vacuum degree in the film forming chamber of the sputtering film forming device reached 1.0×10 -4 After 0.2 Pa, argon as a sputtering gas and oxygen as a reactive gas are introduced into the film forming chamber, and the gas pressure in the film forming chamber is set to 0.2 Pa. It should be noted that argon and oxygen are introduced into the film forming chamber in a volume ratio of 100:10. In addition, as a target of the sputtering device, a sintered body of indium oxide and tin oxide is used, that is, a sintered body containing indium oxide and tin oxide in a mass ratio of 90:10. As a power source for applying voltage to the target, an MFAC power supply is used, the discharge power is set to 4.3 kW, and the film forming temperature (the temperature of the transparent substrate film for forming the primer layer) is set to -8°C.

[0351] In this way, the primer layer is formed on one surface in the thickness direction of the transparent base film (one surface in the thickness direction of the cured resin layer).

[0352] [Formation of barrier layer]

[0353] Next, an alternating laminate was formed on one side of the primer layer in the thickness direction by reactive sputtering, the alternating laminate having, in order toward one side in the thickness direction: a 16 nm thick niobium oxide layer (first layer), a 38 nm thick silicon oxide layer (second layer), a 30 nm thick niobium oxide layer (third layer), and a 98 nm thick silicon oxide layer (fourth layer). The alternating laminate was formed using the following method: Figure 5 The roll-to-roll magnetron sputtering film forming device Z shown in the figure. It should be noted that the device has a plurality of film forming chambers, which can make the working film (transparent base film with a primer layer) move in a roll-to-roll manner and implement the film forming process. In addition, the sputtering film forming device for forming an alternating stack body has Figure 8The details of the magnet unit and sputtering film forming conditions of the second magnetron plasma unit used for forming the alternating stack are shown below.

[0354] In the magnet unit of the second magnetron plasma unit, the first to fourth magnetic pole portions are used, the length L of the opposite side is 10 mm, and the separation distance D between the opposite side and the fixed side (the length of the side) is 20 mm. It should be noted that the second magnetic pole portion and the third magnetic pole portion are set as N poles, and the first magnetic pole portion and the fourth magnetic pole portion are set as S poles. In addition, the magnetization directions of the second magnetic pole portion and the third magnetic pole portion are set to be inclined relative to the thickness direction and the width direction of the fixed component and intersecting with each other toward the center of the film-forming roller, and the magnetization directions of the first magnetic pole portion and the fourth magnetic pole portion are set to be along the width direction of the fixed component (parallel to the width direction of the fixed component). By adopting such a structure, the sputtering angle (angle θ) can be set to about 30 degrees.

[0355] During the deposition of the first layer, vacuum evacuation was performed until the ultimate vacuum degree in the deposition chamber of the sputtering deposition apparatus reached 1.0×10 -4 After 0.5 Pa, argon as a sputtering gas and oxygen as a reactive gas are introduced into the film forming chamber, and the gas pressure in the film forming chamber is set to 0.5 Pa. It should be noted that argon and oxygen are introduced into the film forming chamber in a volume ratio of 100:5. In addition, niobium is used as a target for the sputtering device. As a power source for applying voltage to the target, an MFAC power supply is used, the discharge power is set to 13 kW, and the film forming temperature (the temperature of the transparent substrate film with a primer layer formed by the alternating laminate) is set to -8 °C.

[0356] During the deposition of the second layer, vacuum evacuation was performed until the ultimate vacuum degree in the deposition chamber of the sputtering deposition apparatus reached 1.0×10 -4 After 0.2 Pa, argon as a sputtering gas and oxygen as a reactive gas are introduced into the film forming chamber, and the gas pressure in the film forming chamber is set to 0.2 Pa. It should be noted that argon and oxygen are introduced into the film forming chamber in a volume ratio of 100:30. In addition, silicon is used as a target for the sputtering device. As a power source for applying voltage to the target, an MFAC power supply is used, the discharge power is set to 25 kW, and the film forming temperature (the temperature of the transparent substrate film with a primer layer formed by the alternating laminate) is set to -8 °C.

[0357] The film formation of the third layer was carried out under the same conditions as those for the film formation of the first layer except that the discharge power was set to 25 kW.

[0358] The film formation of the fourth layer was carried out under the same conditions as those for the film formation of the second layer, except that the discharge power was set to 20 kW.

[0359] Thus, an alternating laminate is formed on one side of the primer layer in the thickness direction, and the alternating laminate includes, in order toward one side in the thickness direction: a niobium oxide layer (first layer), a silicon oxide layer (second layer), a niobium oxide layer (third layer), and a silicon oxide layer (fourth layer).

[0360] Then, an antifouling layer with a thickness of 8 nm was formed on one side of the thickness direction of the alternating laminate (one side of the thickness direction of the fourth layer) by vacuum evaporation. As the material of the antifouling layer, a material obtained by drying and solidifying an antifouling layer composition (trade name: SHIN-ETSU SUBELYN KY1903-1, active ingredient: alkoxysilane compound containing a perfluoropolyether skeleton, manufactured by Shin-Etsu Chemical Co., Ltd.) was used as an evaporation source, and the heating temperature of the evaporation source was set to 260°C.

[0361] In this way, an antifouling layer is formed on one side of the silicon oxide layer in the thickness direction. In other words, a barrier layer is formed on one side of the primer layer in the thickness direction. It should be noted that the barrier layer sequentially comprises: a niobium oxide layer (first layer), a silicon oxide layer (second layer), a niobium oxide layer (third layer), a silicon oxide layer (fourth layer) and an antifouling layer toward one side in the thickness direction.

[0362] The barrier film was formed as described above.

[0363] <Production of polarizing plate with barrier film>

[0364] A cycloolefin film (refractive index characteristics: nx>ny>nz, in-plane phase difference: 116nm) as the first phase difference layer and a modified polyethylene film (refractive index characteristics: nz>nx>ny, in-plane phase difference: 35nm) as the second phase difference layer are sequentially attached to the surface of the polarizer of the above-mentioned polarizing plate. The attachment uses an ultraviolet curing adhesive for attaching the polarizer to the protective film. It should be noted that the slow axis of the first phase difference layer is at an angle of 0° relative to the absorption axis of the polarizer, and the slow axis of the second phase difference layer is at an angle of 90° relative to the absorption axis of the polarizer. Furthermore, the above-mentioned barrier film is attached to the surface of the protective film (methacrylic resin film) of the polarizing plate via an acrylic adhesive (thickness: 20μm), thereby obtaining a polarizing plate with a barrier film. It should be noted that the transparent substrate film of the barrier film is attached in contact with the surface of the protective film of the polarizing plate via an acrylic adhesive.

[0365] Example 2

[0366] The polarizing plate with a barrier film of Example 2 was produced in the same manner as the polarizing plate with a barrier film of Example 1, except that an alternating laminated body was formed on one surface in the thickness direction of the primer layer, the alternating laminated body having a 5 nm thick niobium oxide layer (first layer) and a 135 nm thick silicon oxide layer (second layer) in this order toward one side in the thickness direction. That is, in Example 2, the third layer and the fourth layer were not formed in the barrier film.

[0367] Example 3

[0368] In the barrier film, only a silicon oxide layer (second layer) having a thickness of 135 nm was formed on one surface of the primer layer in the thickness direction, and a polarizing plate with a barrier film of Example 3 was produced in the same manner as the polarizing plate with a barrier film of Example 1. That is, in Example 3, the first layer, the third layer, and the fourth layer were not formed in the barrier film.

[0369] Comparative Example 1

[0370] In the barrier film, a sputtering film forming apparatus (specifically, a sputtering film forming apparatus having ... Figure 7 A polarizing plate with a barrier film of Comparative Example 1 was produced in the same manner as the polarizing plate with a barrier film of Example 3 except for the above.

[0371] Comparative Example 2

[0372] In the barrier film, a sputtering film forming apparatus (specifically, having a sputtering film forming apparatus) used in a primer layer forming process is used to form a niobium oxide layer (first layer), a silicon oxide layer (second layer), a niobium oxide layer (third layer), and a silicon oxide layer (fourth layer). Figure 7 A polarizing plate with a barrier film of Comparative Example 2 was produced in the same manner as the polarizing plate with a barrier film of Example 1 except for the above.

[0373] Reference Example 1

[0374] A polarizing plate with a barrier film of Reference Example 1 was produced in the same manner as the polarizing plate with a barrier film of Comparative Example 2 except for the following.

[0375] In the polarizing plate, first, a film formed by stretching a polyvinyl alcohol film with an average degree of polymerization of 2700 and a thickness of 75 μm to 6 times while being iodine-dyed is used as a polarizer. Then, a transparent film with a thickness of 30 μm formed by a modified acrylic polymer having a lactone ring structure is attached to the polarizer. It should be noted that the attachment is made of an adhesive composed of an aqueous solution of a polyvinyl alcohol resin containing an acetoacetyl group (average degree of polymerization of 1200, saponification degree of 98.5 mol%, acetoacetylation degree of 5 mol%) and methylol melamine in a weight ratio of 3:1, and after being attached with a roller laminating machine, it is heated and dried in an oven. In this way, a polarizing plate is obtained.

[0376] Reference Example 2

[0377] A polarizing plate with a barrier film of Reference Example 2 was produced in the same manner as the polarizing plate with a barrier film of Example 1 except for the following.

[0378] In the barrier film, a cured resin coating layer containing silica particles is formed as a barrier layer on one side of the transparent substrate film in the thickness direction (one side of the cured resin layer in the thickness direction). Specifically, a cured resin coating liquid containing silica particles is applied to one side of the transparent substrate film in the thickness direction (one side of the cured resin layer in the thickness direction) using a wire rod. The applied coating liquid is heated at 80°C for 1 minute to dry it and form a coating film. The dried coating film is irradiated with a high-pressure mercury lamp with a cumulative light intensity of 300 mJ / cm 2 The coating film was cured to form a 100 nm thick cured resin coating layer containing silica particles.

[0379] [Preparation of Cured Resin Coating Liquid Containing Silica Particles]

[0380] 100 parts by mass of a multifunctional acrylate containing pentaerythritol triacrylate as the main component (trade name: Viscoat #300, solid content: 100% by mass, manufactured by Osaka Organic Chemical Industry Co., Ltd.), 100 parts by mass of hollow nano-silica particles (trade name: THRULYA5320, solid content: 20% by mass, mass average particle size: 75 nm, manufactured by JGC Catalysts & Chemicals Co., Ltd.), 30 parts by mass of solid nano-silica particles (trade name: MEK-2140Z-AC, solid content: 30% by mass, mass average particle size: 10 nm, manufactured by Nissan Chemical Industries, Ltd.), 12 parts by mass of an additive containing a fluorine element (trade name: KY-1203, solid content: 20% by mass, manufactured by Shin-Etsu Chemical Co., Ltd.), and 3 parts by mass of a photopolymerization initiator (trade name: OMNIRAD907, solid content: 100% by mass, manufactured by BASF) were mixed. To the mixture, a mixed solvent prepared by mixing TBA (tert-butyl alcohol), MIBK (methyl isobutyl ketone) and PMA (propylene glycol monomethyl ether acetate) in a mass ratio of 60:25:15 was added as a diluent solvent so that the total solid content became 4% by mass, and the mixture was stirred to prepare a curing resin coating liquid containing silica particles.

[0381] <Evaluation>

[0382] [density]

[0383] In each of the Examples, Comparative Examples and Reference Example 1, the density of the silicon oxide layer closest to the antifouling layer in the thickness direction was measured by Rutherford Backscattering Spectrometry (RBS). The results are shown in Table 1. It should be noted that the film thickness obtained by the method shown below was used in the calculation of the density.

[0384] In each embodiment, each comparative example and reference example 1, the thickness of the silicon oxide layer closest to the antifouling layer in the thickness direction is measured by observation using a field emission transmission electron microscope (FE-TEM). Specifically, first, a cross-sectional observation sample of the barrier film in each embodiment, each comparative example and reference example 1 is prepared by the FIB microsampling method. In the FIB microsampling method, a FIB device (product name: FB2200, manufactured by Hitachi) is used, and the acceleration voltage is set to 10 kV. Next, the cross section of the barrier film in the cross-sectional observation sample is observed by FE-TEM, and the thickness of the silicon oxide layer closest to the antifouling layer is measured in the observed image. It should be noted that in this observation, a FE-TEM device (trade name: JEM-2800, manufactured by JEOL) is used, and the acceleration voltage is set to 200 kV.

[0385] [Moisture Permeability]

[0386] The polarizing plates with barrier films in each example, each comparative example and each reference example were cut into a 15 cm Φ circular shape as a measurement sample. After the measurement sample was left at a temperature of 40°C and a humidity of 92% RH for 24 hours, the water vapor transmission rate was measured using a water vapor transmission rate measuring device (product name: DELTAPERM, manufactured by Techno Eye) under the test conditions of a temperature of 40°C and a humidity of 90% RH. The results are shown in Table 1.

[0387] [Chroma]

[0388] The polarizing plates with barrier films (100 mm × 50 mm) in each example, each comparative example, and each reference example were placed in a constant temperature and humidity chamber at a temperature of 65°C and a humidity of 90% RH. The chromaticity b of the transmitted light of each polarizing plate with barrier film before (0 hour), 240 hours, and 500 hours after the polarizing plates were placed in the heating and humidification conditions was measured using a spectrophotometer (product name: DOT-3, manufactured by Murakami Color Research Laboratory Co., Ltd.). * The chromaticity b of the transmitted light measured at each hour is calculated by the following formula: * The chromaticity b of the transmitted light measured before entering the heating and humidification conditions * The difference between the initial value and the transmitted light is defined as the change in chromaticity Δb. * The results are shown in Table 1.

[0389] The change in chromaticity of the transmitted light Δb * =(chromaticity b of the transmitted light before entering the heating and humidification conditions * (initial value))-(chromaticity of transmitted light measured at each hour b * )

[0390] [Reflectivity]

[0391] The reflectance of the barrier film in each embodiment, each comparative example and each reference example was measured using an ultraviolet-visible-infrared spectrophotometer (product name: UH-4150, manufactured by Hitachi High Tech Science). A black acrylic plate was attached to the transparent substrate film side of the barrier film using an adhesive as a measurement sample. The measurement was performed at a wavelength of 380 nm to 780 nm. The results are shown in Table 1.

[0392] [Table 1]

[0393]

[0394] It should be noted that the above invention is provided as an exemplary embodiment of the present invention, but it is merely an example and is not to be construed as limiting. Modifications of the present invention that are clear to those skilled in the art are included in the claims.

[0395] Industrial Applicability

[0396] The barrier film of the present invention is used for protecting a polarizing plate used in, for example, an image display device.

Claims

1. A barrier film, wherein: The barrier film comprises: A transparent substrate film having a transparent resin film; and The barrier layer is disposed on one side in the thickness direction of the transparent substrate film. The barrier layer comprises at least one silicon oxide layer and an antifouling layer disposed on one side in the thickness direction of the silicon oxide layer. In the thickness direction, the density of the silicon oxide layer closest to the antifouling layer is 2.35 g / cm 3 above.

2. The barrier film according to claim 1, wherein The transparent base film further includes a cured resin layer disposed on one side in the thickness direction of the transparent resin film.

3. The barrier film according to claim 1, wherein The barrier film further comprises a primer layer, The primer layer is a metal oxide layer, The primer layer is disposed on one side in the thickness direction of the transparent base film and on the other side in the thickness direction of the barrier layer.

4. The barrier film according to claim 1, wherein The barrier layer includes: an alternately stacked body formed of at least one niobium oxide layer and at least one silicon oxide layer; and the antifouling layer disposed on one surface in a thickness direction of the alternately stacked body.

5. The barrier film according to claim 1, wherein The barrier layer is formed of a silicon oxide layer and the antifouling layer disposed on one surface in a thickness direction of the silicon oxide layer.

6. A polarizing plate with a barrier film, comprising: The barrier film according to any one of claims 1 to 5; and A polarizing plate is disposed on the other side in the thickness direction of the barrier film.

7. The polarizing plate with a barrier film according to claim 6, wherein: The polarizing plate comprises a protective film and a polarizer. The polarizing plate is a coating film of a polyvinyl alcohol resin.

8. The polarizing plate with a barrier film according to claim 6, wherein The change in chromaticity of transmitted light under the conditions of 60°C, 90% relative humidity and 240 hours of heating and humidification Δb * Is below 0.5.

Citation Information

Patent Citations

  • Transparent conductive film and method for manufacturing the same

    JP2016179686A

  • Polarizing plate with Anti-reflection layer and method for producing same

    WO2019163461A1